Resin composition

A resin composition with epoxy resin, active ester resin, and a (meth)acrylate compound addresses poor stain removability and crack resistance in circuit boards, enhancing dielectric properties and reducing transmission loss.

CN119192808APending Publication Date: 2024-12-27AJINOMOTO CO INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410818455.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-26
Filing Date
2024-06-24
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing resin compositions with active ester resins for improving dielectric properties in circuit boards suffer from poor stain removability and crack resistance during desmearing treatment, especially when high-filling inorganic fillers are used.

Method used

A resin composition comprising epoxy resin, active ester resin, and a (meth)acrylate compound with an aliphatic group of 10 or more carbon atoms, with specific mass ratios and structural formulations to enhance dielectric properties, stain removability, and crack resistance.

Benefits of technology

The composition achieves a cured product with good dielectric properties, effective stain removal, and improved crack resistance, reducing transmission loss in high-frequency environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004908425460000021
    Figure BDA0004908425460000021
  • Figure BDA0004908425460000022
    Figure BDA0004908425460000022
  • Figure BDA0004908425460000023
    Figure BDA0004908425460000023
Patent Text Reader

Abstract

The present invention addresses the problem of providing a novel resin composition capable of providing a cured product exhibiting good dielectric properties, good stain removability, and good crack resistance. [Solution] A resin composition containing (A) an epoxy resin, (B) an active ester resin, and (C) a (meth) acrylate compound containing an aliphatic group having 10 or more carbon atoms.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a resin composition and further to a resin sheet, a cured product, a circuit board and a semiconductor device. Background Art

[0002] A resin composition containing an epoxy resin and a curing agent thereof can produce a cured product having excellent insulation, heat resistance, adhesion, etc., and is therefore widely used as an insulating material for circuit boards such as printed wiring boards and rewiring boards for semiconductor chip packages.

[0003] On the other hand, with the recent increase in the speed of communication, insulating materials for circuit boards need to have excellent dielectric properties (low dielectric loss tangent) in order to reduce transmission loss when working in a high-frequency environment. As insulating materials with excellent dielectric properties, there are reports that specific curing agents such as active ester resins that can reduce or inhibit the generation of polar groups such as secondary hydroxyl groups in the curing reaction of epoxy resins are used (for example, Patent Documents 1 and 2).

[0004] Prior art literature Patent Document 1: Japanese Patent Application Publication No. 2019-157027 Patent Document 2: Japanese Patent Application Publication No. 2020-94213 Summary of the invention

[0005] Technical problem to be solved by the invention In this regard, if the active ester resin is added to achieve good dielectric properties, the stain removal performance during desmearing treatment will be poor, or cracks will be easily generated after desmearing treatment. In order to achieve better dielectric properties (low dielectric loss tangent), it is desired to use a high-filling inorganic filler, but in this case, it is found that cracks after desmearing treatment tend to become significant.

[0006] An object of the present invention is to provide a novel resin composition capable of producing a cured product having good dielectric properties, good stain removability and good crack resistance.

[0007] Means of solving technical problems The present inventors have conducted intensive studies and, as a result, have found that the above-mentioned problems (technical issues) can be solved by a resin composition having the following structure, thereby completing the present invention.

[0008] That is, the present invention includes the following contents. [1] A resin composition comprising: (A) Epoxy resin, (B) an active ester resin, and (C) A (meth)acrylate compound containing an aliphatic group having 10 or more carbon atoms. [2] The resin composition according to [1], wherein the mass ratio of the component (B) to the component (A) [component (B) / component (A)] is 0.8 or more. [3] The resin composition according to [1] or [2], wherein the content of the component (C) is 0.5% by mass or more when the resin component in the resin composition is 100% by mass. [4] The resin composition according to any one of [1] to [3], wherein the component (C) contains a divalent aliphatic group represented by the following formula (1): [Chemical formula 1] (In formula (1), A C Each independently represents a single bond or a divalent aliphatic group, Ring Z C represents an aliphatic ring optionally having a substituent, * indicates a bond, 2 A C and Ring Z C The total number of carbon atoms is 10 or more). [5] The resin composition according to any one of [1] to [4], wherein the component (C) has a structure represented by the following formula (C1): [Chemical formula 2] (In formula (C1), X each independently represents a (meth)acryloyl group, A 1 Each independently represents a divalent aliphatic group, A 2 each independently represents a divalent aliphatic group having 10 or more carbon atoms, L 1 Each independently represents a divalent linking group, n1 represents a number greater than or equal to 1). [6] The resin composition according to any one of [1] to [5], wherein the component (C) has a structure represented by the following formula (C1-1): [Chemical Formula 3] (In formula (C1-1), X each independently represents a (meth)acryloyl group, A 11 each independently represents an alkylene group having 1 to 12 carbon atoms, A21 each independently represents an alkylene group having 1 to 12 carbon atoms or an alkenylene group having 2 to 12 carbon atoms, Ring Z 1 each independently represents a cycloalkane ring having 4 to 14 carbon atoms which may have a substituent, Ring Z 2 Each independently represents a cycloalkane ring having 4 to 14 carbon atoms which may have a substituent, or a cycloalkene ring having 4 to 14 carbon atoms which may have a substituent, n11 represents a number from 1 to 10). [7] The resin composition according to [6], wherein in formula (C1-1), X each independently represents a (meth)acryloyl group, A 11 represents an alkylene group having 1 carbon atom, A 21 represents an alkylene group having 7 carbon atoms, Ring Z 1 represents a tricyclodecane ring, Ring Z 2 represents a cyclohexane ring substituted with two alkyl groups having 5 to 8 carbon atoms, n11 represents a number from 1 to 5. [8] The resin composition according to any one of [1] to [7], further comprising (E) an inorganic filler. [9] The resin composition according to [8], wherein the content of the component (E) is 40% by mass or more when the nonvolatile component in the resin composition is 100% by mass.

[10] The resin composition according to any one of [1] to [9], further comprising (F) a compound containing a radically polymerizable unsaturated group (excluding the component (C)).

[11] The resin composition according to any one of [1] to

[10] , which is used for an insulating layer of a circuit board.

[12] A resin sheet comprising a support and a layer of the resin composition according to any one of [1] to

[11] provided on the support.

[13] The resin sheet according to

[12] , wherein the support is a thermoplastic resin film or a metal foil.

[14] A cured product of the resin composition according to any one of [1] to

[11] .

[15] A circuit board comprising an insulating layer formed from a cured product of the resin composition according to any one of [1] to

[11] .

[16] A semiconductor device comprising the circuit substrate described in

[15] . Effects of the Invention

[0009] According to the present invention, a novel resin composition can be provided which can provide a cured product having good dielectric properties, good stain removability and good crack resistance. DETAILED DESCRIPTION

[0010] <Explanation of terms> In this specification, the term "aliphatic group" refers to a group obtained by removing one or more hydrogen atoms from an aliphatic compound. Specifically, a monovalent aliphatic group refers to a group obtained by removing one hydrogen atom from an aliphatic compound, and a divalent aliphatic group refers to a group obtained by removing two hydrogen atoms from an aliphatic compound. Here, the aliphatic compound may be an aliphatic compound containing no heteroatoms and consisting only of carbon atoms and hydrogen atoms, or an aliphatic compound containing heteroatoms and consisting of heteroatoms in addition to carbon atoms and hydrogen atoms. In this specification, the term "heteroatom" refers to an atom other than a carbon atom and a hydrogen atom, and examples thereof include an oxygen atom, a nitrogen atom, a sulfur atom, a silicon atom, a halogen atom, and the like.

[0011] In this specification, the term "aliphatic hydrocarbon group" refers to a group obtained by removing one or more hydrogen atoms from an aliphatic compound containing no heteroatoms and consisting only of carbon atoms and hydrogen atoms. Specifically, a monovalent aliphatic hydrocarbon group refers to a group obtained by removing one hydrogen atom from an aliphatic compound containing no heteroatoms, and a divalent aliphatic hydrocarbon group refers to a group obtained by removing two hydrogen atoms from an aliphatic compound containing no heteroatoms. Examples of the monovalent aliphatic hydrocarbon group include an alkyl group optionally having a substituent, a cycloalkyl group optionally having a substituent, an alkenyl group optionally having a substituent, a cycloalkenyl group optionally having a substituent, and an alkapolyenyl group optionally having a substituent (the number of double bonds is preferably 2 to 10, more preferably 2 to 6, further preferably 2 to 4, and further more preferably 2). It may also be formed by a combination of two or more of these groups. In addition, as a divalent aliphatic hydrocarbon group, for example, an alkylene group optionally having a substituent, a cycloalkylene group optionally having a substituent, an alkenylene group optionally having a substituent, a cycloalkenylene group optionally having a substituent, and an alkapolyenylene group optionally having a substituent (the number of double bonds is preferably 2 to 10, more preferably 2 to 6, further preferably 2 to 4, and further more preferably 2). It can also be formed by a combination of two or more of these groups. Here, the alkyl, alkenyl, polyenyl, alkylene, alkenylene, and polyenylene can all be any of a straight chain or a branched chain. In this specification, unless otherwise specified, the number of carbon atoms of the aliphatic hydrocarbon group is preferably 1 or more, more preferably 2 or more or 3 or more, preferably 100 or less, more preferably 80 or less, and further preferably 60 or less, 50 or less, or 40 or less. The number of carbon atoms does not include the number of carbon atoms of the substituent.

[0012] In the present specification, the term "aliphatic group containing heteroatoms" refers to a group obtained by removing one or more hydrogen atoms from an aliphatic compound containing heteroatoms. Specifically, a monovalent aliphatic group containing heteroatoms refers to a group obtained by removing one hydrogen atom from an aliphatic compound containing heteroatoms, and a divalent aliphatic group containing heteroatoms refers to a group obtained by removing two hydrogen atoms from an aliphatic compound containing heteroatoms. In the "aliphatic group containing heteroatoms" in the present specification, the heteroatom may be bonded to any carbon atom constituting the group; for example, (i) it may be bonded to the terminal carbon; (ii) it may also exist between carbon-carbon bonds. In addition, in the "aliphatic group containing heteroatoms" in the present specification, the bond may extend from a carbon atom or from a heteroatom. The aliphatic group containing heteroatoms may be any saturated or unsaturated aliphatic group containing heteroatoms, and may also have a cyclic structure. Examples of the monovalent heteroatom-containing aliphatic group include, for example, a heteroalkyl group optionally having a substituent, a heteroalkenyl group optionally having a substituent, a heteroalkynyl group optionally having a substituent, a heteropolyenyl group optionally having a substituent, and a monovalent aliphatic heterocyclic group optionally having a substituent, and may be formed by a combination of two or more of these groups. Examples of the monovalent heteroatom-containing aliphatic group include -O-, -S-, -C(=O)-, -S(=O)-, -S(=O)-, -O ... 2 -、-N(R')-、-Si(R') 2 - and combinations thereof, wherein the divalent group is bonded to a monovalent aliphatic carbocyclic group or a monovalent aliphatic heterocyclic group (wherein R' represents a hydrogen atom or a substituent described below. The same applies to the following). Examples of divalent aliphatic groups containing heteroatoms include, for example, heteroalkylene groups optionally having substituents, heteroalkenylene groups optionally having substituents, heteroalkynylene groups optionally having substituents, heteropolyenylene groups optionally having substituents, and divalent aliphatic heterocyclic groups optionally having substituents. It may also be formed by a combination of two or more of these groups. Examples of divalent aliphatic groups containing heteroatoms include groups selected from -O-, -S-, -C(=O)-, -S(=O)-, -S(=O) 2 -、-N(R')-、-Si(R') 2- and a divalent group formed by a chemical bond of a divalent aliphatic carbocyclic group or a divalent aliphatic heterocyclic group in a combination thereof. In this specification, the number of heteroatoms of an aliphatic group containing a heteroatom is preferably 1 or more, 2 or more, or 3 or more, preferably 30 or less, 25 or less, or 20 or less, unless otherwise specified. In addition, unless otherwise specified, the number of carbon atoms is preferably 1 or more, more preferably 2 or more, or 3 or more, preferably 100 or less, more preferably 80 or less, and further preferably 60 or less, 50 or less, or 40 or less. The number of heteroatoms or carbon atoms does not include the number of heteroatoms or carbon atoms of the substituent.

[0013] In this specification, the term "aliphatic ring" refers to a ring other than an aromatic ring. The aliphatic ring may have a double bond in a part of the ring. In addition, the aliphatic ring may be a monocyclic aliphatic ring, or a bridged aliphatic ring such as a bicyclic or tricyclic ring. The aliphatic ring may be an aliphatic carbocyclic ring having only carbon atoms as ring atoms, or may be an aliphatic heterocyclic ring having heteroatoms as ring atoms in addition to carbon atoms. In this specification, as long as there is no special description, the carbon number of the aliphatic ring is preferably 3 or more, more preferably 4 or more or 5 or more, and more preferably 6 or more, and its upper limit is preferably 24 or less, more preferably 18 or less or 14 or less, and more preferably 10 or less. As a monocyclic aliphatic ring, for example, a cyclopropane ring, a cyclobutane ring, a cyclopentane ring, a cyclohexane ring, a cycloheptane ring, a cyclooctane ring, a cyclononane ring, a cyclodecane ring, a cycloundecane ring, a cyclododecane ring, etc. can be cited. Examples of the bridged aliphatic ring include bicycloheptane rings such as bicyclo[4.1.0]heptane, bicyclo[3.2.0]heptane, bicyclo[3.1.1]heptane, and bicyclo[2.2.1]heptane; bicyclooctane rings such as bicyclo[4.2.0]octane, bicyclo[4.1.1]octane, bicyclo[3.2.1]octane, and bicyclo[2.2.2]octane; bicyclononane rings such as bicyclo[4.2.1]nonane, and bicyclo[3.3.1]nonane; bicyclodecane rings such as bicyclo[4.4.0]decane, bicyclo[4.2.2]decane, and bicyclo[3.3.2]decane; and bicyclodecane rings such as bicyclo[4.3.2]undecane, bicyclo[3 .3.3]undecane and the like; bicyclododecane rings such as bicyclo[4.3.3]dodecane; tricycloheptane rings such as tricyclo[2.2.1.0(2,6)]heptane and [2.2.1.0(3,5)]heptane; tricyclooctane rings such as tricyclo[3.2.1.0(2,4)]octane and tricyclo[3.2.1.0(2,7)]octane; tricyclononane rings such as tricyclo[4.2.1.0(3,7)]nonane and tricyclo[4.2.1.0(4,8)]nonane; tricyclodecane rings such as tricyclo[5.2.1.0(2,6)]decane and tricyclo[3.3.1.1(3,7)]decane.

[0014] In the present specification, the term "optionally having a substituent" with respect to a compound or a group refers to both the case where hydrogen atoms of the compound or group are not substituted with a substituent and the case where part or all of the hydrogen atoms of the compound or group are substituted with a substituent.

[0015] In the present specification, the term "substituent" means a halogen atom, an alkyl group, an alkenyl group, a cycloalkyl group, an alkoxy group, a cycloalkyloxy group, an alkylthio group, a cycloalkylthio group, an aryl group, an aryloxy group, an arylthio group, an arylalkyl group, an arylalkoxy group, a monovalent heterocyclic group, an alkylidene group, an acyl group, an acyloxy group, a hydroxyl group, an amino group, a silyl group, a carboxyl group, a sulfo group, a cyano group, a nitro group, a mercapto group and an oxo group, unless otherwise specified.

[0016] As the halogen atom used as the substituent, for example, fluorine atom, chlorine atom, bromine atom and iodine atom can be mentioned. The alkyl group used as the substituent may be either linear or branched. The number of carbon atoms of the alkyl group is preferably 1 to 12, more preferably 1 to 10, and further preferably 1 to 8. The alkenyl group used as the substituent may be either linear or branched. The number of carbon atoms of the alkenyl group is preferably 2 to 12, more preferably 2 to 10, and further preferably 2 to 8. The number of carbon atoms of the cycloalkyl group used as the substituent is preferably 3 to 12, and further preferably 3 to 10. The alkoxy group used as the substituent may be either linear or branched. The number of carbon atoms of the alkoxy group is preferably 1 to 12, more preferably 1 to 10, and further preferably 1 to 8. The number of carbon atoms of the cycloalkoxy group used as the substituent is preferably 3 to 12, and further preferably 3 to 10. The alkylthio group used as the substituent may be either linear or branched. The number of carbon atoms in the alkylthio group is preferably 1 to 12, more preferably 1 to 10, and further preferably 1 to 8. The number of carbon atoms in the cycloalkylthio group used as a substituent is preferably 3 to 12, and more preferably 3 to 10. The number of carbon atoms in the aryl group used as a substituent is preferably 6 to 14, and more preferably 6 to 10. The number of carbon atoms in the aryloxy group used as a substituent is preferably 6 to 14, and more preferably 6 to 10. The number of carbon atoms in the arylthio group used as a substituent is preferably 6 to 14, and more preferably 6 to 10. The number of carbon atoms in the aralkyl group used as a substituent is preferably 7 to 15, and more preferably 7 to 11. The number of carbon atoms in the arylalkoxy group used as a substituent is preferably 7 to 15, and more preferably 7 to 11. The monovalent heterocyclic group used as a substituent refers to a group obtained by removing one hydrogen atom from a heterocyclic ring of a heterocyclic compound. The number of carbon atoms in the monovalent heterocyclic group is preferably 3 to 15, and more preferably 3 to 9. The monovalent heterocyclic group also includes a monovalent aromatic heterocyclic group (heteroaryl). The alkylidene group used as a substituent refers to a group obtained by removing two hydrogen atoms from the same carbon atom of an alkane. The number of carbon atoms of the alkylidene group is preferably 1 to 12, more preferably 1 to 6, and particularly preferably 1 to 3. The acyl group used as a substituent is a group represented by the formula: -C(=O)-R (wherein R is an alkyl group or an aryl group). The alkyl group represented by R may be either linear or branched. The number of carbon atoms of the acyl group is preferably 2 to 13, and more preferably 2 to 7. The acyloxy group used as a substituent is a group represented by the formula: -OC(=O)-R (wherein R has the same meaning as above). The number of carbon atoms of the acyloxy group is preferably 2 to 13, and more preferably 2 to 7. The above-mentioned substituent may further have a substituent (sometimes referred to as a "secondary substituent"). As a secondary substituent, the same group as the above-mentioned substituent may be used unless otherwise specified.

[0017] In this specification, "(meth)acrylate compound" refers to a compound containing both acrylate compounds and methacrylate compounds, and means a compound containing one or more acryloyloxy groups or methacryloyloxy groups in the molecule. In this specification, in order to indicate both acryloyloxy and methacryloyloxy groups, it is also referred to as "(meth)acryloyloxy", and in order to indicate both acryloyl and methacryloyl groups, it is also referred to as "(meth)acryloyl".

[0018] Hereinafter, the present invention will be described in detail with reference to the embodiments and examples. However, the present invention is not limited to the following embodiments and examples, and can be implemented with any modifications within the scope of the claims and their equivalents.

[0019] [Resin composition] The resin composition of the present invention is characterized by comprising (A) an epoxy resin, (B) an active ester resin, and (C) a (meth)acrylate compound containing an aliphatic group having 10 or more carbon atoms.

[0020] As described above, the insulating material of the circuit board is required to exhibit good dielectric properties (low dielectric loss tangent) in order to reduce the transmission loss when working in a high-frequency environment. In this regard, the present inventors have found that after the active ester resin is added to a degree that achieves good dielectric properties, the insulating material obtained has a tendency to have poor stain removal during decontamination treatment or to easily crack after decontamination treatment. In addition, it is confirmed that when the inorganic filler is further added to a high degree in order to achieve better dielectric properties, the generation of cracks after decontamination treatment becomes significant.

[0021] In contrast, according to the present invention, a (meth)acrylate compound containing an aliphatic group having 10 or more carbon atoms is used in combination with an epoxy resin and an active ester resin, and a cured product having good dielectric properties, good stain removal properties, and good crack resistance can be obtained. Thus, the present invention can provide a cured product having good dielectric properties, good stain removal properties, and good crack resistance, and has a significant contribution to realizing a circuit substrate having a circuit that has a desired characteristic while advantageously reducing transmission loss when operating in a high-frequency environment.

[0022] Hereinafter, each component will be described.

[0023] <(A) Epoxy resin> The resin composition of the present invention contains an epoxy resin as the component (A).

[0024] Examples of the epoxy resin include bisphenol epoxy resins, dicyclopentadiene epoxy resins, trisphenol epoxy resins, naphthol novolac epoxy resins, phenol novolac epoxy resins, tert-butyl-catechol epoxy resins, naphthalene epoxy resins, naphthol epoxy resins, anthracene epoxy resins, glycidylamine epoxy resins, glycidyl ester epoxy resins, cresol novolac epoxy resins, biphenyl epoxy resins, linear aliphatic epoxy resins, epoxy resins having a butadiene structure, alicyclic epoxy resins, heterocyclic epoxy resins, spiro ring-containing epoxy resins, cyclohexane epoxy resins, cyclohexanedimethanol epoxy resins, naphthylene ether epoxy resins, trimethylol epoxy resins, and tetraphenylethane epoxy resins. Bisphenol epoxy resin refers to epoxy resin having a bisphenol structure, and examples thereof include bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, and bisphenol AF epoxy resin. Biphenyl epoxy resin refers to epoxy resin having a biphenyl structure, wherein the biphenyl structure optionally has substituents such as alkyl, alkoxy, and aryl. Therefore, bixylenol epoxy resin and biphenyl aralkyl epoxy resin are also included in biphenyl epoxy resin. One epoxy resin may be used alone, or two or more epoxy resins may be used in combination.

[0025] As the epoxy resin, an aromatic epoxy resin is preferred. Here, the aromatic epoxy resin refers to an epoxy resin having an aromatic ring in its molecule.

[0026] The epoxy resin preferably has two or more epoxy groups in one molecule. When the nonvolatile component of the epoxy resin is 100% by mass, the proportion of the epoxy resin having two or more epoxy groups in one molecule is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more.

[0027] Among epoxy resins, there are epoxy resins that are liquid at a temperature of 20° C. (hereinafter referred to as “liquid epoxy resin”) and epoxy resins that are solid at a temperature of 20° C. (hereinafter referred to as “solid epoxy resin”).

[0028] As the liquid epoxy resin, a liquid epoxy resin having two or more epoxy groups in one molecule is preferred.

[0029] As liquid epoxy resins, preferred are bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol AF type epoxy resins, naphthalene type epoxy resins, glycidyl ester type epoxy resins, glycidyl amine type epoxy resins, phenol novolac type epoxy resins, alicyclic epoxy resins such as alicyclic epoxy resins having an ester skeleton, cyclohexane type epoxy resins, cyclohexanedimethanol type epoxy resins, and epoxy resins having a butadiene structure.

[0030] Specific examples of liquid epoxy resins include "HP-4032", "HP-4032-D", and "HP-4032-SS" (naphthalene-type epoxy resins) manufactured by DIC Corporation; "828US", "jER828EL", "825", and "EPIKOTE828EL" (bisphenol A-type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER807" and "1750" (bisphenol F-type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER152" (phenol novolac-type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "630" and "630LSD" (glycidylamine-type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "ZX1059" (a mixture of bisphenol A-type epoxy resin and bisphenol F-type epoxy resin) manufactured by Nippon Steel Chemical Materials Co., Ltd.; "EX-721" (glycidyl ester-type epoxy resin) manufactured by Nagase ChemteX Corporation; and "CELLOXIDE 2021P" (alicyclic epoxy resin with an ester skeleton); "PB-3600" manufactured by Daicel Corporation (epoxy resin with a butadiene structure); "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane type epoxy resin) manufactured by Nippon Steel Chemical Materials Co., Ltd., etc.

[0031] As the solid epoxy resin, a solid epoxy resin having three or more epoxy groups in one molecule is preferred, and an aromatic solid epoxy resin having three or more epoxy groups in one molecule is more preferred.

[0032] As the solid epoxy resin, preferred are biphenylol type epoxy resin, naphthalene type epoxy resin, naphthalene type tetrafunctional epoxy resin, cresol novolac type epoxy resin, dicyclopentadiene type epoxy resin, trisphenol type epoxy resin, naphthol type epoxy resin, biphenyl type epoxy resin, naphthylene ether type epoxy resin, anthracene type epoxy resin, bisphenol A type epoxy resin, bisphenol AF type epoxy resin, and tetraphenylethane type epoxy resin.

[0033] Specific examples of solid epoxy resins include "HP-4032H" (naphthalene-type epoxy resin) manufactured by DIC Corporation; "HP-4700" and "HP-4710" (naphthalene-type tetrafunctional epoxy resin) manufactured by DIC Corporation; "N-690" (cresol novolac-type epoxy resin) manufactured by DIC Corporation; "N-695" (cresol novolac-type epoxy resin) manufactured by DIC Corporation; "HP-7200HH", "HP-7200H", "HP-7200H" and "HP-7200H" manufactured by DIC Corporation. 0" (dicyclopentadiene type epoxy resin); "EXA-7311", "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", "HP6000" (naphthylene ether type epoxy resin) manufactured by DIC Corporation; "EPPN-502H" (trisphenol type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC-7000L" (naphthol novolac type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC-3000H" (naphthol novolac type epoxy resin) manufactured by Nippon Kayaku Co., Ltd. ”, “NC-3000”, “NC-3000L”, “NC-3100” (biphenyl type epoxy resin); “ESN-475V” (naphthalene type epoxy resin) manufactured by Nippon Steel Chemicals Co., Ltd., “ESN-485” (naphthol novolac type epoxy resin) manufactured by Nippon Steel Chemicals Co., Ltd.; “YX4000H”, “YX4000”, “YL6121” (biphenyl type epoxy resin) manufactured by Mitsubishi Chemical Corporation; “YX4000HK” (biphenyl type epoxy resin) manufactured by Mitsubishi Chemical Corporation Epoxy resin); "YX8800" manufactured by Mitsubishi Chemical Corporation (anthracene type epoxy resin); "PG-100" and "CG-500" manufactured by Osaka Gas Chemical Co., Ltd.; "YL7760" manufactured by Mitsubishi Chemical Corporation (bisphenol AF type epoxy resin); "YL7800" manufactured by Mitsubishi Chemical Corporation (fluorene type epoxy resin); "jER1010" manufactured by Mitsubishi Chemical Corporation (solid bisphenol A type epoxy resin); "jER1031S" manufactured by Mitsubishi Chemical Corporation (tetraphenylethane type epoxy resin), etc.

[0034] In the resin composition of the present invention, as the epoxy resin, only a liquid epoxy resin may be included, only a solid epoxy resin may be included, or a liquid epoxy resin and a solid epoxy resin may be included in combination. When a liquid epoxy resin and a solid epoxy resin are used in combination, their amount ratio (liquid epoxy resin: solid epoxy resin) is preferably 1:0.01 to 1:50, more preferably 1:0.05 to 1:20, and further preferably 1:0.1 to 1:10 in terms of mass ratio.

[0035] The epoxy equivalent of the epoxy resin is preferably 50 g / eq. to 5000 g / eq., more preferably 50 g / eq. to 3000 g / eq., further preferably 80 g / eq. to 2000 g / eq., and further more preferably 110 g / eq. to 1000 g / eq. The epoxy equivalent is the mass of the epoxy resin containing 1 equivalent of epoxy groups. The epoxy equivalent can be measured according to JIS K7236.

[0036] The weight average molecular weight (Mw) of the epoxy resin is preferably 100 to 5000, more preferably 250 to 3000, and even more preferably 400 to 1500. The Mw of the epoxy resin can be measured as a value in terms of polystyrene by gel permeation chromatography (GPC).

[0037] In the combination of (B) component and (C) component described later, from being able to bring the cured product that presents good dielectric properties and good contamination removal and crack resistance at the same time, and being able to bring the cured product that mechanical properties are also excellent, the content of (A) component in the resin combination, when the resin component in the resin combination is set to 100 mass %, is preferably more than 5 mass %, more preferably more than 10 mass %, further preferably more than 12 mass %, more than 14 mass % or more than 15 mass %. The upper limit of this content is not particularly limited, and can be determined according to the characteristic required by the resin combination, for example, can be less than 60 mass %, less than 50 mass % or less than 40 mass %, etc.

[0038] In the present invention, the "resin component" referred to in the resin composition means a component obtained by removing an inorganic filler described below from a non-volatile component constituting the resin composition.

[0039] <(B) Active ester resin> The resin composition of the present invention contains an active ester resin as the component (B).

[0040] As active ester curing agent, a compound having more than one active ester group in one molecule can be used. Wherein, as active ester curing agent, preferably phenolic esters, thiophenolic esters, N-hydroxylamine esters, esters of heterocyclic hydroxy compounds, etc. have more than two compounds with high reactive ester groups in one molecule. The active ester curing agent is preferably obtained by the condensation reaction of carboxylic acid compounds and / or thiocarboxylic acid compounds with hydroxy compounds and / or thiol compounds. Particularly from the viewpoint of improving heat resistance, preferably active ester curing agents from carboxylic acid compounds, more preferably active ester curing agents obtained from carboxylic acid compounds and hydroxy compounds, further preferably active ester curing agents obtained from carboxylic acid compounds and aromatic hydroxy compounds.

[0041] As the carboxylic acid compound, any of an aromatic carboxylic acid compound and an aliphatic carboxylic acid compound may be used, and examples thereof include benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, pyromellitic acid, and halides thereof.

[0042] Examples of the aromatic hydroxy compound include (i) addition polymerization products of unsaturated aliphatic cyclic compounds having two double bonds in one molecule and phenols, (ii) various bisphenol compounds, (iii) aromatic polyols having two or more hydroxyl groups bonded to carbon atoms on an aromatic ring, and (iv) aromatic monohydric alcohols having one hydroxyl group bonded to a carbon atom on an aromatic ring. Examples of the addition polymerization products of unsaturated aliphatic cyclic compounds and phenols include addition polymerization products of unsaturated aliphatic cyclic compounds such as dicyclopentadiene, tetrahydroindene, norbornadiene, limonene, and vinylcyclohexene and phenols which may have a substituent (e.g., phenol, cresol, xylenol, ethylphenol, propylphenol, vinylphenol, allylphenol, phenylphenol, benzylphenol, and halogenated phenols). Specifically, examples include dicyclopentadiene-phenol addition polymerization products. Examples of the bisphenol compound include bisphenol A, bisphenol F, bisphenol AF, bisphenol AP, bisphenol B, bisphenol BP, bisphenol C, and bisphenol M. Examples of the aromatic polyol in which two or more hydroxyl groups are bonded to carbon atoms on an aromatic ring include hydroquinone, resorcinol, catechol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucinol, pyrogallol, and phenolic novolac resin. Examples of the aromatic monohydric alcohol having one hydroxyl group bonded to a carbon atom on the aromatic ring include phenol, cresol, xylenol, ethylphenol, propylphenol, vinylphenol, allylphenol, phenylphenol, benzylphenol, halogenated phenols, naphthol, methylnaphthol, dimethylnaphthol, ethylnaphthol, propylnaphthol, vinylnaphthol, allylnaphthol, phenylnaphthol, benzylnaphthol, halogenated naphthols, and the like.

[0043] From the viewpoint of being able to enjoy the effect of the present invention more, as a specific example of a preferred active ester resin, an active ester resin comprising a dicyclopentadiene type diphenol structure, an active ester resin comprising a naphthalene structure, an active ester resin comprising an acetylated product of a linear phenolic resin, and an active ester resin comprising a benzoylated product of a linear phenolic resin can be cited. Among them, in combination with the component (C) described later, from the viewpoint of being able to simultaneously present a cured product having better dielectric properties and better stain removal and crack resistance, an active ester resin comprising a naphthalene structure and an active ester resin comprising a dicyclopentadiene type diphenol structure are more preferably included. "Dicyclopentadiene type diphenol structure" represents a divalent structural unit formed by phenylene-dicyclopentylene (ジシクロペンチレン)-phenylene.

[0044] As the component (B), commercial products can be used. Examples of the commercial products include "EXB-9451", "EXB-9460", "EXB-9460S", "HPC-8000-65T", "HPC-8000H-65MT", and "HPC-8000L-65MT" (manufactured by DIC Corporation) as active ester resins containing a dicyclopentadiene-type diphenol structure; "EXB-8100L-65T", "EXB-8150-60T", "EXB-8150-62T", "EXB-9416-70BK", and "HPC-8100L-65T" as active ester resins containing a naphthalene structure. As the active ester resin containing phosphorus, "EXB9401" (manufactured by DIC Corporation) can be cited; as the active ester resin of the acetylated product of the linear phenolic resin, "DC808" (manufactured by Mitsubishi Chemical Corporation) can be cited; as the active ester resin of the benzoylated product of the linear phenolic resin, "YLH1026", "YLH1030" and "YLH1048" (manufactured by Mitsubishi Chemical Corporation) can be cited; as the active ester resin containing a styryl group and a naphthalene structure, "PC1300-02-65MA" (manufactured by Air Water Corporation) and the like can be cited.

[0045] The component (B) may be used alone or in combination of two or more at any ratio.

[0046] The active ester group equivalent of the component (B) is preferably 50 g / eq. to 500 g / eq., more preferably 50 g / eq. to 400 g / eq., and even more preferably 100 g / eq. to 300 g / eq. The active ester group equivalent is the mass of the active ester resin per 1 equivalent of active ester groups.

[0047] From the viewpoint of the resin combination that easily realizes bringing good dielectric properties, the content of (B) component in the resin combination, when the resin component in the resin combination is set to 100 mass %, is preferably more than 10 mass %, more preferably more than 20 mass %, further preferably more than 25 mass % or more than 30 mass %. The upper limit of this content is not particularly limited, and can be determined according to the characteristic required by the resin combination, for example, can be less than 60 mass %, less than 55 mass % or less than 50 mass %, etc.

[0048] In the resin composition of the present invention, from the viewpoint of bringing about a cured product exhibiting good dielectric properties, the mass ratio of component (B) to component (A) (component (B) / component (A)) is preferably greater than 0.6, more preferably greater than 0.8, and further preferably greater than 1. As described above, according to the resin composition of the present invention using component (C), even when component (B) is included to an extent that excellent dielectric properties can be achieved, a cured product exhibiting good contamination removal properties and good crack resistance can be brought about. For example, in the resin composition of the present invention, the mass ratio of component (B) to component (A) can be increased to greater than 1.1, greater than 1.2, or greater than 1.25. The upper limit of the mass ratio (component (B) / component (A)) can be, for example, less than 2, less than 1.9, less than 1.8, etc.

[0049] <(C) (Meth)acrylate compound containing an aliphatic group having 10 or more carbon atoms> The resin composition of the present invention is characterized by containing, as component (C), a (meth)acrylate compound containing an aliphatic group having 10 or more carbon atoms.

[0050] In combination with the components (A) and (B), the component (C) preferably contains two or more (meth)acryloyl groups in the molecule from the viewpoint of providing a cured product exhibiting good dielectric properties and good stain removability and crack resistance.

[0051] In combination with the components (A) and (B), it is important that the component (C) contains an aliphatic group having 10 or more carbon atoms from the viewpoint of providing a cured product exhibiting good dielectric properties as well as good stain removability and crack resistance.

[0052] The aliphatic group having 10 or more carbon atoms contained in the component (C) may be any of a straight chain or a branched chain, and may also contain an aliphatic ring in its structure. The number of carbon atoms in the aliphatic group is as described above, and from the viewpoint of being able to enjoy the effect of the present invention more, it is preferably 12 or more, more preferably 14 or more, 16 or more, 18 or more, or 20 or more, and further preferably 22 or more, 24 or more, 26 or more, 28 or more, or 30 or more, and its upper limit is preferably 100 or less, and more preferably 80 or less, 60 or less, 50 or less, or 40 or less.

[0053] In the combination with the components (A) and (B), from the viewpoint of being able to realize a cured product exhibiting better dielectric properties and better stain removal and crack resistance, the aliphatic group having 10 or more carbon atoms is preferably an aliphatic group containing an aliphatic ring (preferably an aliphatic carbocyclic ring). From the same viewpoint, the aliphatic group having 10 or more carbon atoms is preferably an aliphatic hydrocarbon group. In a preferred embodiment, the component (C) contains an aliphatic group having 10 or more carbon atoms containing an aliphatic ring, and more preferably contains an aliphatic hydrocarbon group having 10 or more carbon atoms containing an aliphatic carbocyclic ring. The preferred range of the carbon number of the aliphatic group is as described above.

[0054] Among them, in combination with the components (A) and (B), from the viewpoint of being able to better enjoy the effects of the present invention, the aliphatic group having 10 or more carbon atoms contained in the component (C) is preferably an alkylene group optionally having a substituent, a cycloalkylene group optionally having a substituent, an alkenylene group optionally having a substituent, a cycloalkenylene group optionally having a substituent, an optionally substituted polyalkenylene group (the number of double bonds is preferably 2 to 4, more preferably 2), and a divalent aliphatic group formed by a combination of two or more of these groups.

[0055] The substituents which these aliphatic groups may have are as described above, and among them, from the viewpoint of enjoying the effects of the present invention more, preferably at least one selected from a halogen atom, an alkyl group, an alkenyl group, a cycloalkyl group, an alkoxy group and a cycloalkoxy group, and more preferably at least one selected from a fluorine atom, an alkyl group having 1 to 10 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms and a cycloalkoxy group having 3 to 10 carbon atoms.

[0056] In a preferred embodiment in which the effects of the present invention can be more effectively achieved, the component (C) contains a divalent aliphatic group represented by the following formula (1).

[0057] [Chemical formula 4] (In formula (1), A CEach independently represents a single bond or a divalent aliphatic group, Ring Z C represents an aliphatic ring optionally having a substituent, * indicates a bond, 2 A C and Ring Z C The total number of carbon atoms is 10 or more.)

[0058] For the divalent aliphatic group represented by formula (1), the two A C and Ring Z C The total number of carbon atoms in the group is 10 or more, which meets the above-mentioned “aliphatic group having 10 or more carbon atoms”.

[0059] In formula (1), A C Each independently represents a single bond or a divalent aliphatic group. C The divalent aliphatic group shown is as described above, but from the viewpoint of enjoying the effect of the present invention more, it is preferably an alkylene group optionally having a substituent or an alkenylene group optionally having a substituent, and more preferably an alkylene group having 1 to 12 carbon atoms optionally having a substituent or an alkenylene group having 2 to 12 carbon atoms optionally having a substituent.

[0060] In formula (1), ring Z C represents an aliphatic ring which may have a substituent. C The aliphatic ring in is as described above. From the viewpoint of being able to enjoy the effects of the present invention more, it is preferably an aliphatic carbon ring, and more preferably a cycloalkane ring or a cycloolefin ring. Here, the cycloalkane ring or the cycloolefin ring may be a bridged ring such as a bicyclic or tricyclic ring. The number of carbon atoms in the aliphatic ring is as described above, but from the viewpoint of being able to enjoy the effects of the present invention more, it is preferably 4 or more, more preferably 6 or more, and its upper limit is preferably 14 or less, more preferably 10 or less. Therefore, in a preferred embodiment, ring Z C It is a cycloalkane ring having 4 to 14 carbon atoms which may have a substituent, or a cycloalkene ring having 4 to 14 carbon atoms which may have a substituent.

[0061] In formula (1), A C The divalent aliphatic group or ring Z C The substituents that the aliphatic ring in optionally has are as described above, and from the viewpoint of being able to enjoy the effects of the present invention more, preferably at least one selected from a halogen atom, an alkyl group, an alkenyl group, a cycloalkyl group, an alkoxy group and a cycloalkoxy group, and more preferably at least one selected from a fluorine atom, an alkyl group having 1 to 10 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms and a cycloalkoxy group having 3 to 10 carbon atoms.

[0062] As mentioned above, in formula (1), the two A C and Ring Z C The total number of carbon atoms is 10 or more, and is preferably 50 or less, and more preferably 40 or less, from the viewpoint of more effectively enjoying the effects of the present invention.

[0063] In the combination with the components (A) and (B), from the viewpoint of achieving a cured product exhibiting better dielectric properties and better stain removability and crack resistance, particularly preferred examples of the divalent aliphatic group represented by the formula (1) are shown below.

[0064] In a preferred embodiment, in formula (1), A C each independently represents an alkylene group having 1 to 12 carbon atoms or an alkenylene group having 2 to 12 carbon atoms, Ring Z C represents a cycloalkane ring having 4 to 14 carbon atoms which may have a substituent or a cycloalkene ring having 4 to 14 carbon atoms which may have a substituent, wherein the substituent is one or more selected from the group consisting of a fluorine atom, an alkyl group having 1 to 10 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, and a cycloalkoxy group having 3 to 10 carbon atoms, 2 A C and Ring Z C The total number of carbon atoms is 10 or more and 50 or less.

[0065] In a more preferred embodiment, in formula (1), A C each independently represents an alkylene group having 1 to 8 carbon atoms or an alkenylene group having 2 to 8 carbon atoms, Ring Z C represents a cycloalkane ring having 6 to 10 carbon atoms which may have a substituent or a cycloalkene ring having 6 to 10 carbon atoms which may have a substituent, wherein the substituent is at least one selected from the group consisting of a fluorine atom, an alkyl group having 1 to 10 carbon atoms, and an alkenyl group having 2 to 10 carbon atoms, 2 A C and Ring Z C The total number of carbon atoms is 10 or more and 40 or less.

[0066] In combination with the components (A) and (B), the component (C) preferably contains one or more, more preferably two or more, and even more preferably three or more divalent aliphatic groups represented by the formula (1) in the molecule, from the viewpoint of being able to achieve a cured product exhibiting better dielectric properties and better stain removal properties and crack resistance. The upper limit of the number of divalent aliphatic groups represented by the formula (1) in the molecule is preferably 20 or less, more preferably 15 or less, and even more preferably 10 or less.

[0067] In a preferred embodiment, the component (C) has a structure represented by the following formula (C1).

[0068] [Chemical formula 5] (In formula (C1), X each independently represents a (meth)acryloyl group, A 1 Each independently represents a divalent aliphatic group, A 2 each independently represents a divalent aliphatic group having 10 or more carbon atoms, L 1 Each independently represents a divalent linking group, n1 represents a number greater than 1.)

[0069] -Divalent aliphatic group A 1 - In formula (C1), A 1 Each independently represents a divalent aliphatic group. 1 The divalent aliphatic group shown is as described above, preferably an alkylene group optionally having a substituent, a cycloalkylene group optionally having a substituent, an alkenylene group optionally having a substituent, a cycloalkenylene group optionally having a substituent, a polyenylene group optionally having a substituent (the number of double bonds is preferably 2 to 4, and more preferably 2), and a divalent aliphatic group formed by a combination of two or more of these groups. The preferred range of the number of carbon atoms of the alkylene group, cycloalkylene group, alkenylene group, cycloalkenylene group, and polyenylene group in these divalent aliphatic groups is as described above for the aliphatic hydrocarbon group.

[0070] From the viewpoint of enjoying the effect of the present invention more, A 1 The number of carbon atoms of the divalent aliphatic group is preferably 2 or more, more preferably 4 or more, and further preferably 6 or more, and the upper limit is preferably 40 or less, more preferably 30 or less, 20 or less, or 15 or less.

[0071] Among them, from the viewpoint of being able to enjoy the effect of the present invention more, A 1 The divalent aliphatic group represented by is preferably a divalent aliphatic group represented by the following formula (C2).

[0072] [Chemical formula 6] (In formula (C2), A 11 Each independently represents a single bond or a divalent aliphatic group, Ring Z 1represents an aliphatic ring optionally having a substituent, * indicates a bond. )

[0073] In formula (C2), A 11 Each independently represents a single bond or a divalent aliphatic group. 11 The divalent aliphatic group shown is as described above, and from the viewpoint of being able to enjoy the effects of the present invention more, it is preferably a divalent aliphatic hydrocarbon group, and more preferably an alkylene group optionally having a substituent, an alkenylene group optionally having a substituent, or a polyenylene group optionally having a substituent (the number of double bonds is preferably 2 to 4, and more preferably 2). 11 The preferred range of carbon number of the alkylene, alkenylene and polyalkenylene in the formula (1) is as described above for the aliphatic hydrocarbon group, and the preferred types of substituents are also as described above. In particular, from the viewpoint of enjoying the effects of the present invention more, they may be different from those for A in the formula (1). C Same as described.

[0074] In formula (C2), ring Z 1 represents an aliphatic ring which may have a substituent. 1 The aliphatic ring in is as described above, and from the viewpoint of being able to enjoy the effects of the present invention more, an aliphatic carbon ring is preferred, and a cycloalkane ring optionally having a substituent or a cycloolefin ring optionally having a substituent is more preferred. Here, the cycloalkane ring or cycloolefin ring may be a bridged ring such as a bicyclic or tricyclic ring. Ring Z 1 The preferred range of carbon number of the cycloalkane ring and the cycloalkene ring in the formula (1) is as described above for the aliphatic ring, and the preferred types of substituents are also as described above. In particular, from the viewpoint of enjoying the effects of the present invention more, they may be different from those for the ring Z in the formula (1). C Same as described.

[0075] From the viewpoint of enjoying the effect of the present invention more, 2 A 11 and Ring Z 1 The total number of carbon atoms is preferably 6 or more, more preferably 8 or more, further preferably 10 or more, and the upper limit is preferably 40 or less, more preferably 30 or less, 20 or less, or 15 or less.

[0076] When 2 A 11 and Ring Z 1 When the total number of carbon atoms is 10 or more, the divalent aliphatic group represented by formula (C2) may be a divalent aliphatic group having 10 or more carbon atoms represented by the above-mentioned formula (1).

[0077] -Divalent aliphatic group A 2 - In formula (C1), A 2Each independently represents a divalent aliphatic group having 10 or more carbon atoms. 2 The divalent aliphatic group having 10 or more carbon atoms is as described above including preferred examples thereof.

[0078] Among them, from the viewpoint of being able to enjoy the effect of the present invention more, A 2 The divalent aliphatic group having 10 or more carbon atoms is preferably a divalent aliphatic group represented by the following formula (C3).

[0079] [Chemical formula 7] (In formula (C3), A 21 Each independently represents a single bond or a divalent aliphatic group, Ring Z 2 represents an aliphatic ring optionally having a substituent, * indicates a bond, 2 A 21 and Ring Z 2 The total number of carbon atoms is 10 or more.)

[0080] In formula (C3), A 21 Each independently represents a single bond or a divalent aliphatic group. 21 The divalent aliphatic group shown is as described above, and from the viewpoint of being able to enjoy the effects of the present invention more, it is preferably a divalent aliphatic hydrocarbon group, and more preferably an alkylene group optionally having a substituent, an alkenylene group optionally having a substituent, or a polyenylene group optionally having a substituent (the number of double bonds is preferably 2 to 4, and more preferably 2). 21 The preferred range of carbon number of the alkylene, alkenylene and polyalkenylene in the formula (1) is as described above for the aliphatic hydrocarbon group, and the preferred types of substituents are also as described above. In particular, from the viewpoint of enjoying the effects of the present invention more, they may be different from those for A in the formula (1). C Same as described.

[0081] In formula (C3), ring Z 2 represents an aliphatic ring which may have a substituent. 2 The aliphatic ring in is as described above, and from the viewpoint of being able to enjoy the effects of the present invention more, it is preferably an aliphatic carbon ring, and more preferably a cycloalkane ring optionally having a substituent or a cycloalkene ring optionally having a substituent. Here, the cycloalkane ring or cycloalkene ring may be a bridged ring such as a bicyclic or tricyclic ring. Ring Z 2The preferred range of carbon number of the cycloalkane ring and the cycloalkene ring in the formula (1) is as described above for the aliphatic ring, and the preferred types of substituents are also as described above. In particular, from the viewpoint of enjoying the effects of the present invention more, they may be different from those for the ring Z in the formula (1). C Same as described.

[0082] 2 A 21 and Ring Z 2 The total number of carbon atoms is 10 or more, and is preferably 50 or less, and more preferably 40 or less, from the viewpoint of more effectively enjoying the effects of the present invention.

[0083] From the viewpoint of achieving a better effect of the present invention, the divalent aliphatic group having 10 or more carbon atoms represented by formula (C3) is preferably a divalent aliphatic group having 10 or more carbon atoms represented by formula (1) described above.

[0084] -Divalent linking group L 1 - In formula (C1), L 1 Each independently represents a divalent linking group.

[0085] As L 1 The divalent linking group is not particularly limited as long as it is a divalent group composed of one or more (e.g., 1 to 50, 1 to 30, 1 to 20, or 1 to 10) backbone atoms selected from carbon atoms, oxygen atoms, nitrogen atoms, and sulfur atoms. However, from the viewpoint of enjoying the effects of the present invention more, it is preferably selected from a divalent hydrocarbon group having 1 to 10 carbon atoms, which may have a substituent, -O-, -CO-, -S-, -SO-, -SO 2 -, -CONH-, -NHCO-, -COO- or -OCO- and a divalent connecting group in the group consisting of: -, -CONH-, -NHCO-, -COO- or -OCO- and combinations thereof.

[0086] From the perspective of being able to enjoy the effects of the present invention more, L 1 The number of carbon atoms of the divalent linking group is preferably 10 or less, more preferably 6 or less, further preferably 4 or less, and the lower limit thereof is 1 or more.

[0087] Among them, from the viewpoint of being able to enjoy the effect of the present invention more, L 1 The divalent linking group shown is preferably -CONH-, -NHCO-, -COO- or -OCO-.

[0088] -n1- In formula (C1), n1 represents a number of 1 or more.

[0089] From the viewpoint of more enjoying the effects of the present invention, n1 is preferably a number of 20 or less, more preferably 15 or less, further preferably 10 or less, 8 or less, 6 or less, or 5 or less.

[0090] In combination with the components (A) and (B), from the viewpoint of achieving a cured product exhibiting better dielectric properties and better stain removal properties and crack resistance, in a preferred embodiment, the component (C) has a structure represented by the following formula (C1-1).

[0091] [Chemical formula 8] (In formula (C1-1), X, A 11 , A 21 、Ring Z 1 、Ring Z 2 It has the same meaning as above. In addition, n11 represents a number greater than 1.)

[0092] X.A 11 , A 21 、Ring Z 1 and Ring Z 2 In addition, n11 represents a number greater than 1, and from the viewpoint of being able to enjoy the effects of the present invention more, it represents a number preferably less than 20, more preferably less than 15, and further preferably less than 10, less than 8, less than 6, or less than 5.

[0093] In the combination with the components (A) and (B), from the viewpoint of being able to realize a cured product exhibiting better dielectric properties and better stain removal properties and crack resistance, the composition of the component A is preferably 11 -Ring Z 1 -A 11 The blocks formed by A 21 -Ring Z 2 -A 21 The formed blocks are preferably all divalent aliphatic groups having 10 or more carbon atoms represented by the above-mentioned formula (1).

[0094] In combination with the components (A) and (B), from the viewpoint of achieving a cured product exhibiting better dielectric properties and better stain removability and crack resistance, examples of the structure represented by the formula (C1-1) are particularly preferred as follows.

[0095] In a preferred embodiment, in formula (C1-1), X each independently represents a (meth)acryloyl group, A 11 and A 21 Each independently represents an alkylene group having 1 to 12 carbon atoms or an alkenylene group having 2 to 12 carbon atoms, and ring Z 1 and Ring Z 2Each independently represents a cycloalkane ring having 4 to 14 carbon atoms which may have a substituent, or a cycloalkene ring having 4 to 14 carbon atoms which may have a substituent, wherein the substituent represents one or more selected from the group consisting of a fluorine atom, an alkyl group having 1 to 10 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, and a cycloalkoxy group having 3 to 10 carbon atoms, n11 represents a number from 1 to 10.

[0096] In a more preferred embodiment, in formula (C1-1), X each independently represents a (meth)acryloyl group, A 11 Each independently represents an alkylene group having 1 to 12 carbon atoms (preferably 1 to 6, more preferably 1 to 4), A 21 Each independently represents an alkylene group having 1 to 12 carbon atoms (preferably 1 to 10, more preferably 4 to 10), or an alkenylene group having 2 to 12 carbon atoms (preferably 2 to 10, more preferably 4 to 10), Ring Z 1 Each independently represents a cycloalkane ring having 4 to 14 carbon atoms (preferably 6 to 10 carbon atoms) which may have a substituent, wherein the substituent represents at least one selected from the group consisting of a fluorine atom, an alkyl group having 1 to 10 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, and a cycloalkoxy group having 3 to 10 carbon atoms, and ring Z 2 Each independently represents a cycloalkane ring having 4 to 14 carbon atoms (preferably 6 to 10 carbon atoms) which may have a substituent, or a cycloalkene ring having 4 to 14 carbon atoms (preferably 6 to 10 carbon atoms) which may have a substituent, wherein the substituent is selected from at least one of a fluorine atom, an alkyl group having 1 to 10 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, and a cycloalkoxy group having 3 to 10 carbon atoms, n11 represents a number from 1 to 10.

[0097] In a particularly preferred embodiment, in formula (C1-1), X each independently represents a (meth)acryloyl group, A 11 represents an alkylene group having 1 carbon atom, A 21 represents an alkylene group having 7 carbon atoms, Ring Z 1 represents a tricyclodecane ring, Ring Z 2 represents a cyclohexane ring substituted with two alkyl groups having 5 to 8 carbon atoms, n11 represents a number from 1 to 5.

[0098] In combination with the components (A) and (B), from the viewpoint of being able to realize a cured product exhibiting further improved dielectric properties and further improved stain removal properties and crack resistance, the (meth)acryloyl equivalent of the component (C) is preferably 300 g / eq. or more, more preferably 350 g / eq. or more, 400 g / eq. or more, or 450 g / eq. or more, and the upper limit thereof is preferably 4000 g / eq. or less, more preferably 3000 g / eq. or less, 2500 g / eq. or less, 2400 g / eq. or less, 2200 g / eq. or less, or 2000 g / eq. or less. The (meth)acryloyl equivalent represents the mass of the component (C) per 1 equivalent of (meth)acryloyl groups.

[0099] For example, the component (C) may be aliphatic dihydroxy compound (HO-A 1 -OH, preferably HO-A 11 -Ring Z 1 -A 11 -OH; in the formula, A 1 , A 11 、Ring Z 1 has the same meaning as above) and aliphatic dicarboxylic acid compound (HOOC-A 2 -COOH, preferably HOOC-A 21 -Ring Z 2 -A 21 -COOH; where A 2 , A 21 、Ring Z 2 The terminal of the ester compound obtained by the reaction of (meth)acrylate is modified to produce (in the above formula (C1), L 1 In this case, n1 in (C1) or n11 in (C1-1) can be adjusted by adjusting the degree of reaction between the aliphatic dihydroxy compound and the aliphatic dicarboxylic acid compound.

[0100] As the component (C), a commercially available product may be used. Examples of such commercially available products include "PEAM1769" (manufactured by Designer Molecules Inc.), which is a (meth)acrylate compound containing a divalent aliphatic group having 10 or more carbon atoms represented by formula (1).

[0101] In the combination with (A) component and (B) component, from the viewpoint of being able to realize a cured product that presents further better dielectric properties and further better stain removal and crack resistance, the content of (C) component in the resin composition, when the resin component in the resin composition is set to 100% by mass, is preferably 0.5% by mass or more, more preferably 1% by mass or more, more preferably 1.5% by mass or more, 2% by mass or more, 2.5% by mass or more, 3% by mass or more, 3.5% by mass or more or 4% by mass or more. The upper limit of the content is not particularly limited, and can be determined according to the characteristics required by the resin composition. In the combination with (A) component and (B) component, from the viewpoint of being able to realize a cured product that presents better dielectric properties and further better stain removal and crack resistance, it is preferably 20% by mass or less, more preferably 15% by mass or less, more preferably 12% by mass or less, 10% by mass or less, 8% by mass or less or 6% by mass or less.

[0102] From the viewpoint of being able to better enjoy the effects of the present invention, the mass ratio of the component (C) to the component (B) (component (C) / component (B)) is preferably 0.05 or more, more preferably 0.06 or more, 0.08 or more, or 0.1 or more, and the upper limit is preferably 0.5 or less, more preferably 0.4 or less, 0.3 or less, or 0.2 or less.

[0103] <(D) Other curing agents> The resin composition of the present invention may further contain a curing agent other than the component (B) (also referred to as “other curing agent”) as the component (D).

[0104] Examples of the component (D) include phenolic curing agents, naphthol curing agents, acid anhydride curing agents, cyanate curing agents, carbodiimide curing agents, and amine curing agents. The component (D) may be used alone or in combination of two or more.

[0105] As phenolic curing agents and naphthol curing agents, those having a phenolic structure are preferred from the viewpoint of heat resistance and water resistance. In addition, from the viewpoint of adhesion with the conductor layer, nitrogen-containing phenolic curing agents and nitrogen-containing naphthol curing agents are preferred, and phenolic curing agents containing a triazine skeleton and naphthol curing agents containing a triazine skeleton are more preferred.

[0106] Specific examples of phenolic curing agents and naphthol curing agents include "MEH-7700", "MEH-7810", "MEH-7851", and "MEH-8000H" manufactured by Meiwa Chemicals; "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd.; "SN-170", "SN-180", "SN-190", "SN-475", "SN-485", "SN-495", "SN-495V", and "SN-375" manufactured by Nippon Steel Chemicals Co., Ltd. ", "SN-395"; "TD-2090", "TD-2090-60M", "LA-7052", "LA-7054", "LA-1356", "LA-3018", "LA-3018-50P", "EXB-9500", "HPC-9500", "KA-1160", "KA-1163", "KA-1165" manufactured by DIC Corporation; "GDP-6115L", "GDP-6115H", "ELPC 75" and other products manufactured by Qunrong Chemical Co., Ltd.

[0107] Examples of the acid anhydride curing agent include curing agents having one or more acid anhydride groups in one molecule. Specific examples of the acid anhydride curing agent include phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, hydrogenated methylnadic anhydride, trialkyltetrahydrophthalic anhydride, dodecenylsuccinic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, trimellitic anhydride, pyromellitic anhydride, dicarboxylic anhydride, and the like. Benzophenone tetracarboxylic dianhydride, biphenyl tetracarboxylic dianhydride, naphthalene tetracarboxylic dianhydride, oxydiphthalic dianhydride, 3,3'-4,4'-diphenylsulfone tetracarboxylic dianhydride, 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-C]furan-1,3-dione, ethylene glycol bis(trimellitic anhydride), styrene-maleic acid resin obtained by copolymerization of styrene and maleic acid, etc. As commercially available products of anhydride-based curing agents, "MH-700" manufactured by Shin Nippon Rika Co., Ltd., etc. can be cited.

[0108] Examples of the cyanate curing agent include difunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate, oligo(3-methylene-1,5-phenylene cyanate), 4,4'-methylenebis(2,6-dimethylphenylcyanate), 4,4'-ethylidene diphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyano)phenylpropane, 1,1-bis(4-cyanophenylmethane), bis(4-cyano-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanophenyl-1-(methylethylidene))benzene, bis(4-cyanophenyl)sulfide and bis(4-cyanophenyl)ether; polyfunctional cyanate resins derived from phenol novolac resins and cresol novolac resins; and prepolymers obtained by triazinization of a portion of these cyanate resins. Specific examples of cyanate curing agents include "PT30" and "PT60" manufactured by Arxada (linear phenolic resin-type multifunctional cyanate resins), "ULL-950S" (multifunctional cyanate resin), "BA230", "BA230S75" (prepolymers obtained by triazine-forming a trimer with part or all of bisphenol A dicyanate), etc.

[0109] Specific examples of carbodiimide-based curing agents include CARBODILITE (registered trademark) V-03 (carbodiimide group equivalent: 216 g / eq.), V-05 (carbodiimide group equivalent: 262 g / eq.), and V-07 (carbodiimide group equivalent: 200 g / eq.); V-09 (carbodiimide group equivalent: 200 g / eq.); and Stabaxol (registered trademark) P (carbodiimide group equivalent: 302 g / eq.) manufactured by LANXESS.

[0110] Examples of the amine curing agent include curing agents having one or more amino groups in one molecule, such as aliphatic amines, polyether amines, alicyclic amines, aromatic amines, etc. Specific examples of the amine curing agent include 4,4'-methylenebis(2,6-dimethylaniline), diphenyldiaminosulfone, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylsulfone, 3,3'-diaminodiphenylsulfone, metaphenylenediamine, metaphenylenediamine, diethyltoluenediamine, 4,4'-diaminodiphenyl ether, 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dihydroxybenzidine, 2,2-bis(3-amino- 4-hydroxyphenyl)propane, 3,3-dimethyl-5,5-diethyl-4,4-diphenylmethanediamine, 2,2-bis(4-aminophenyl)propane, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis(4-(4-aminophenoxy)phenyl)sulfone, bis(4-(3-aminophenoxy)phenyl)sulfone, etc. As the amine-based curing agent, commercially available products can be used, for example, "KAYABOND C-200S", "KAYABOND C-100", "KAYAHARD AA", "KAYAHARD AB", "KAYAHARD AS" manufactured by Nippon Kayaku Co., Ltd., and "EPICURE W" manufactured by Mitsubishi Chemical Corporation can be mentioned.

[0111] When the resin composition of the present invention includes component (D), the content of component (D) in the resin composition can be determined according to the characteristics required by the resin composition, and when the resin component in the resin composition is set to 100% by mass, it can be, for example, 0.1% by mass or more, preferably 1% by mass or more, more preferably 2% by mass or more, and further preferably 3% by mass or more. The upper limit of the content of component (D) is not particularly limited, and can be, for example, 20% by mass or less, 15% by mass or less, 10% by mass or less, etc.

[0112] As mentioned above, from the viewpoint of bringing a cured product presenting good dielectric properties, the resin composition of the present invention includes active ester resin, i.e., component (B). In the resin composition of the present invention, when the total of the non-volatile components of component (B) and component (D) is set to 100% by mass, the content of component (B) is preferably more than 50% by mass, more preferably more than 60% by mass, further preferably more than 70% by mass, more than 75% by mass, or more than 80% by mass. The upper limit of the content shared by component (B) in the total of component (B) and component (D) is not particularly limited, and can be 100% by mass, for example, can also be less than 95% by mass, less than 90% by mass, etc.

[0113] <(E) Inorganic fillers> The resin composition of the present invention may further contain an inorganic filler as the component (E). By containing the component (E), the thermal expansion coefficient and the dielectric loss tangent tend to be further reduced.

[0114] As the material of (E) component, for example, silicon dioxide, aluminum oxide, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum silicate, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate, calcium zirconate, zirconium phosphate and zirconium tungstate phosphate, etc. can be cited. Among them, silicon dioxide is particularly preferred. As silicon dioxide, for example, amorphous silicon dioxide, fused silica, crystalline silicon dioxide, synthetic silicon dioxide, hollow silica, etc. can be cited. In addition, as silicon dioxide, spherical silicon dioxide is preferably used. (E) component can be used alone or in combination of two or more.

[0115] Commercially available products of the component (E) include, for example, "SP60-05" and "SP507-05" manufactured by Nippon Steel Chemical Materials Co., Ltd.; "YC100C", "YA050C", "YA050C-MJE", "YA010C", "SC2500SQ", "SO-C4", "SO-C2", and "SO-C1" manufactured by Yaduma Co., Ltd.; "UFP-30", "DAW-03", and "FB-105FD" manufactured by Denka Co., Ltd.; "Silfil NSS-3N", "Silfil NSS-4N", and "Silfil NSS-5N" manufactured by Tokuyama Co., Ltd.; and "Cellspheres" and "MGH-005" manufactured by Pacific Cement Co., Ltd.

[0116] The average particle size of the (E) component is not particularly limited, preferably less than 10 μm, more preferably less than 5 μm, more preferably less than 3 μm, less than 2 μm, less than 1 μm or less than 0.7 μm. The lower limit of the average particle size is not particularly limited, preferably more than 0.01 μm, more preferably more than 0.05 μm, more preferably more than 0.07 μm, more than 0.1 μm or more than 0.2 μm. The average particle size of the (E) component can be measured by a laser diffraction / scattering method based on Mie scattering theory. Specifically, a particle size distribution of an inorganic filler can be prepared by a laser diffraction scattering particle size distribution measuring device with a volume basis, and the median diameter is measured as the average particle size. The sample can be measured using a sample obtained by weighing 100 mg of an inorganic filler and 10 g of methyl ethyl ketone into a vial and dispersing it with ultrasound for 10 minutes. For the measurement sample, a laser diffraction particle size distribution measuring device is used, the wavelength of the light source is set to blue and red, and the volume-based particle size distribution of the inorganic filler is measured by a flow cell method, and the average particle size is calculated as the median particle size based on the obtained particle size distribution. As a laser diffraction particle size distribution measuring device, for example, "LA-960" made by Horiba Manufacturing Co., Ltd. can be cited.

[0117] The specific surface area of ​​the component (E) is not particularly limited, but is preferably 0.1 m 2 / g or more, more preferably 0.5m 2 / g or more, more preferably 1m 2 / g or more, 3m 2 / g or above or 5m 2 The upper limit of the specific surface area is not particularly limited, but is preferably 100 m 2 / g or less, more preferably 80m 2 / g or less, more preferably 60m 2 / g or less, 50m 2 / g or below or 40m 2 The specific surface area of ​​the component (E) can be obtained by adsorbing nitrogen gas on the surface of a sample using a specific surface area measuring apparatus (Macsorb HM-1210 manufactured by Mountech) according to the BET method and calculating the specific surface area using the BET multipoint method.

[0118] (E) component is preferably surface treated with an appropriate surface treatment agent. By performing surface treatment, the moisture resistance and dispersibility of (E) component can be improved. As the surface treatment agent, for example, vinyl silane coupling agent, epoxy silane coupling agent, styrene silane coupling agent, (meth) acrylic silane coupling agent, amino silane coupling agent, isocyanurate silane coupling agent, urea silane coupling agent, mercapto silane coupling agent, isocyanate silane coupling agent, anhydride silane coupling agent and other silane coupling agents; non-silane coupling-alkoxysilane compounds such as methyltrimethoxysilane and phenyltrimethoxysilane; silazane compounds, etc. The surface treatment agent can be used alone or in combination of two or more.

[0119] Commercially available products of the surface treatment agent include, for example, “KBM403” (3-glycidoxypropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., “KBM803” (3-mercaptopropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., “KBE903” (3-aminopropyltriethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., “KBM573” (N-phenyl-3-aminopropyltrimethoxysilane) manufactured by Shin-Etsu Chemical Co., Ltd., and “SZ-31” (hexamethyldisilazane) manufactured by Shin-Etsu Chemical Co., Ltd.

[0120] From the viewpoint of improving the dispersibility of the inorganic filler, the degree of surface treatment by the surface treatment agent is preferably within a predetermined range. Specifically, 100% by mass of the inorganic filler is preferably surface treated with 0.2 to 5% by mass of the surface treatment agent.

[0121] The degree of surface treatment by the surface treatment agent can be evaluated by the carbon content per unit surface area of ​​the inorganic filler. From the viewpoint of improving the dispersibility of the inorganic filler, the carbon content per unit surface area of ​​the inorganic filler is preferably 0.02 mg / m 2 More preferably 0.1 mg / m 2 More preferably, 0.2 mg / m 2 On the other hand, from the viewpoint of preventing the melt viscosity of the resin composition or the melt viscosity of the sheet form from increasing, 1.0 mg / m 2 Below, more preferably 0.8 mg / m 2 Below, more preferably 0.5 mg / m 2Below. The amount of carbon per unit surface area of ​​the component (E) can be measured after the surface-treated inorganic filler is cleaned with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK can be added as a solvent to the inorganic filler that has been surface-treated with a surface treatment agent, and ultrasonic cleaning is performed at 25°C for 5 minutes. After removing the supernatant and drying the solid components, the amount of carbon per unit surface area of ​​the inorganic filler is measured using a carbon analyzer. As a carbon analyzer, "EMIA-320V" manufactured by Horiba, Ltd., etc. can be used.

[0122] When the resin composition of the present invention includes (E) component, from the viewpoint of the resin composition that easily realizes bringing lower dielectric loss tangent or thermal expansion coefficient, the content of (E) component in the resin composition, when the non-volatile component in the resin composition is set to 100 mass %, for example, can be more than 40 mass %, preferably more than 50 mass %, more preferably more than 60 mass %, more than 65 mass % or more than 70 mass %. As described above, according to the present invention using (C) component in combination with (A) component and (B) component, even in the case of such high matching inorganic filler material, it is also possible to bring a cured product with good crack resistance. The upper limit of the content of the (E) component is not particularly limited, for example, can be less than 90 mass %, less than 85 mass %, etc.

[0123] <(F) Compound containing a radically polymerizable unsaturated group> The resin composition of the present invention may further contain a compound containing a free radical polymerizable unsaturated group different from the component (C) as the component (F). By including the component (F) in combination with the component (C), it is easy to achieve a resin composition that provides a cured product with further better dielectric properties, and therefore it is preferred.

[0124] As (F) component, as long as there are more than 1 (preferably more than 2) free radical polymerizable unsaturated groups in 1 molecule, its type is not particularly limited. As (F) component, for example, there can be cited compounds having more than one group selected from maleimide, vinyl, allyl, styryl, vinylphenyl, acryloyl, methacryloyl, fumaryl and maleyl as free radical polymerizable unsaturated groups. Wherein, in combination with (C) component, from the viewpoint of easily realizing the resin composition of the cured product presenting further better dielectric properties, (F) component preferably includes more than one selected from maleimide compounds, allyl compounds, styryl compounds and (meth) acrylic acid compounds.

[0125] As the maleimide compound, the type is not particularly limited as long as it has one or more (preferably two or more) maleimide groups (2,5-dihydro-2,5-dioxo-1H-pyrrol-1-yl) in one molecule. Examples of maleimide compounds include: (1) "BMI-3000J", "BMI-5000", "BMI-1400", "BMI-1500", "BMI-1700", "BMI-689" (all Designer (a) maleimide compounds containing an aliphatic skeleton (a divalent aliphatic group with more than 10 carbon atoms as described in component (C), particularly preferably an aliphatic skeleton with 36 carbon atoms derived from a dimer acid or a dimer diamine) such as "SLK-6895" and "SLK-1500" (manufactured by Shin-Etsu Chemical Co., Ltd.); (2) maleimide compounds containing an indane skeleton as described in the technical bulletin No. 2020-500211 of the Japan Invention Association; (3) maleimide compounds containing an aromatic ring skeleton directly bonded to the nitrogen atom of the maleimide group such as "MIR-3000-70MT" (manufactured by Nippon Kayaku Co., Ltd.), "BMI-4000" (manufactured by Yamato Chemical Co., Ltd.), and "BMI-80" (manufactured by KI Chemical Co., Ltd.).

[0126] As an allyl compound, as long as it has one or more (preferably two or more) allyl groups in one molecule, its type is not particularly limited, and it may be a monomer or an oligomer. As an allyl compound, for example, aromatic carboxylic acid allyl ester compounds such as diallyl diphenate, triallyl trimellitate, diallyl phthalate, diallyl isophthalate, diallyl terephthalate, diallyl 2,6-naphthalene dicarboxylate, and diallyl 2,3-naphthalene dicarboxylate; isocyanuric acid allyl ester compounds such as 1,3,5-triallyl isocyanurate and 1,3-diallyl-5-glycidyl isocyanurate; 2,2-bis[3-allyl] Aromatic allyl compounds containing epoxy groups such as bis[3-allyl-4-(3,4-dihydro-2H-1,3-benzoxazin-3-yl)phenyl]methane; aromatic allyl compounds containing benzoxazine such as bis[3-allyl-4-(3,4-dihydro-2H-1,3-benzoxazin-3-yl)phenyl]methane; aromatic allyl compounds containing ethers such as 1,3,5-triallyl ether benzene; allyl silane compounds such as diallyldiphenylsilane; resins each containing a plurality of benzene rings and allyl groups. Commercially available allyl compounds include, for example, "TAIC" (1,3,5-triallyl isocyanurate) manufactured by Nippon Chemical Industry Co., Ltd., "DAD" (diallyl biphenyl dicarboxylate) manufactured by Nisshoku Techno Fine Chemical Co., Ltd., "TRIAM-705" (triallyl trimellitate) manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., and Nisshoku Techno Fine Chemical Co., Ltd. The trade names "DAND" (2,3-diallyl naphthoate) manufactured by Chemical Co., Ltd., "ALP-d" (bis[3-allyl-4-(3,4-dihydro-2H-1,3-benzoxazin-3-yl)phenyl]methane) manufactured by Shikoku Chemical Co., Ltd., "RE-810NM" (2,2-bis[3-allyl-4-(glycidyloxy)phenyl]propane) manufactured by Nippon Kayaku Co., Ltd., "DA-MGIC" (1,3-diallyl-5-glycidyl isocyanurate) manufactured by Shikoku Chemical Co., Ltd., and "NE-V-1100-70T" (a resin containing multiple benzene rings and allyl groups) manufactured by DIC Corporation, etc.

[0127] As the styryl compound, the type is not particularly limited as long as it has one or more (preferably two or more) styryl groups or vinylphenyl groups in one molecule, and it may be a monomer or an oligomer. Examples of the styryl compound include low molecular weight (molecular weight less than 1000) styryl compounds such as divinylbenzene, 2,4-divinyltoluene, 2,6-divinylnaphthalene, 1,4-divinylnaphthalene, 4,4'-divinylbiphenyl, 1,2-bis(4-vinylphenyl)ethane, 2,2-bis(4-vinylphenyl)propane, and bis(4-vinylphenyl)ether; and high molecular weight (molecular weight greater than 1000) styryl compounds such as vinylbenzyl-modified polyphenylene ether resins and styrene-divinylbenzene copolymers. Examples of commercially available styrene-based compounds include “ODV-XET (X03)”, “ODV-XET (X04)”, and “ODV-XET (X05)” (styrene-divinylbenzene copolymers) manufactured by Nippon Steel Chemical Materials Co., Ltd. and “OPE-2St 1200” and “OPE-2St 2200” (vinyl benzyl-modified polyphenylene ether resins) manufactured by Mitsubishi Gas Chemical Co., Ltd.

[0128] The (meth)acrylic compound is not particularly limited in type as long as it has one or more (preferably two or more) (meth)acryloyl groups in one molecule, and may be a monomer or an oligomer (except for the compound that is component (C)). Examples of the (meth)acrylic acid compound include aliphatic (meth)acrylate compounds of low molecular weight (molecular weight less than 1000) such as cyclohexane-1,4-dimethanol di(meth)acrylate, cyclohexane-1,3-dimethanol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,8-octanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, glycerol tri(meth)acrylate, and pentaerythritol tetra(meth)acrylate; and dioxane diol (meth)acrylate. low molecular weight (molecular weight) esters such as bisphenol A di(meth)acrylate, ... isocyanurate-containing (meth)acrylate compounds with a molecular weight of less than 1000; isocyanurate-containing (meth)acrylate compounds with a low molecular weight (molecular weight less than 1000) such as tris(3-hydroxypropyl)isocyanurate tri(meth)acrylate, tris(2-hydroxyethyl)isocyanurate tri(meth)acrylate, and ethoxylated isocyanurate tri(meth)acrylate; and high molecular weight (molecular weight of 1000 or more) acrylate compounds such as (meth)acrylic acid-modified polyphenylene ether resin. Examples of commercially available (meth)acrylic compounds include “A-DOG” (dioxanediol diacrylate) manufactured by Shin-Nakamura Chemical Industry Co., Ltd., “DCP-A” (tricyclodecane dimethanol diacrylate) and “DCP” (tricyclodecane dimethanol dimethacrylate) manufactured by Kyoeisha Chemical Co., Ltd., “KAYARAD R-684” (tricyclodecane dimethanol diacrylate) and “KAYARAD R-604” (dioxanediol diacrylate) manufactured by Nippon Kayaku Co., Ltd., and “SA9000” and “SA9000-111” (methacrylic acid-modified polyphenylene ether) manufactured by SABIC.

[0129] The component (F) may be used alone or in combination of two or more at any ratio.

[0130] The free radical polymerizable unsaturated group equivalent of the (F) component is preferably 250 g / eq. to 1200 g / eq., and more preferably 300 g / eq. to 1100 g / eq. The free radical polymerizable unsaturated group equivalent represents the mass of the (F) component per 1 equivalent of the free radical polymerizable unsaturated group. When the free radical polymerizable unsaturated group equivalent of the (F) component is within the above range, the effect of the present invention can be significantly obtained.

[0131] The Mw of the component (F) is preferably 1000 to 40000, and more preferably 1500 to 35000. The Mw of the component (F) can be measured as a value in terms of polystyrene by a GPC method.

[0132] When the component (F) is contained, the content of the component (F) in the resin composition is preferably 2% by mass or more, more preferably 3% by mass or more, or 4% by mass or more, based on 100% by mass of the resin component in the resin composition, from the viewpoint of being able to achieve a resin composition that can provide a cured product exhibiting better dielectric properties and better stain removability and crack resistance in combination with the component (C). The upper limit is preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 20% by mass or less.

[0133] <(G) Organic fillers> The resin composition of the present invention may further contain an organic filler as the component (G).

[0134] As the organic filler, an organic filler containing a rubber component can be widely used. As the rubber component contained in the organic filler, for example, silicone elastomers such as polydimethylsiloxane can be cited; olefin thermoplastic elastomers such as polybutadiene, polyisoprene, polychloroprene, ethylene-vinyl acetate copolymer, styrene-butadiene copolymer, styrene-isoprene copolymer, styrene-isobutylene copolymer, acrylonitrile-butadiene copolymer, isoprene-isobutylene copolymer, isobutylene-butadiene copolymer, ethylene-propylene-diene terpolymer, ethylene-propylene-butylene terpolymer, etc.; thermoplastic elastomers such as acrylic thermoplastic elastomers such as poly(meth) propyl acrylate, poly(meth) butyl acrylate, poly(meth) cyclohexyl acrylate, poly(meth) octyl acrylate, etc. can be mixed with the rubber component. Silicone rubbers such as polyorganosiloxane rubber can be mixed. The glass transition temperature (Tg) of the rubber component contained in the rubber particles is, for example, 0°C or lower, preferably -10°C or lower, more preferably -20°C or lower, and further preferably -30°C or lower.

[0135] In one embodiment, the organic filler material is a core-shell rubber particle composed of "a core particle containing a rubber component as listed above" and "a shell portion formed by graft copolymerization of a monomer component copolymerizable with the rubber component contained in the core particle". The core-shell type mentioned here does not necessarily refer only to those in which the core particle and the shell portion can be clearly distinguished, but also includes those in which the boundary between the core particle and the shell portion is unclear, and the core particle may not be completely covered by the shell portion.

[0136] Specific examples of the organic filler containing a rubber component include "CHT" manufactured by Cheil Industries; "B602" manufactured by Techno UMG; "PARALOID EXL-2602", "PARALOID EXL-2603", "PARALOID EXL-2655", "PARALOID EXL-2311", "PARALOID EXL-2313", "PARALOID EXL-2315", "PARALOID KM-330", "PARALOID KM-336P", "PARALOID KCZ-201" manufactured by Dow; "Metablen C-223A", "Metablen E-901", "Metablen S-2001", "Metablen W-450A", "Metablen SRK-200" manufactured by Mitsubishi Rayon Co., Ltd.; "KANE ACE M-511", "KANE ACEM-600", "KANE ACE M-400", "KANE ACE M-580", "KANE ACE MR-01", "STAPHYLOID AC3355", "STAPHYLOID AC3816", "STAPHYLOID AC3832", "STAPHYLOID AC4030", "STAPHYLOID AC3364" manufactured by AICA Industries, Ltd. These are core-shell type rubber particles.

[0137] When (G) component is included, the content of (G) component in the resin composition, when the resin component in the resin composition is set to 100% by mass, is preferably 0.5% by mass or more, more preferably 1% by mass or more, and further preferably 2% by mass or more. The upper limit of this content is preferably below 10% by mass, more preferably below 8% by mass, below 6% by mass or below 5% by mass.

[0138] <(H) Curing Accelerator> The resin composition of the present invention may further contain a curing accelerator as the component (H).

[0139] Examples of the component (H) include phosphorus-based curing accelerators, amine-based curing accelerators, imidazole-based curing accelerators, guanidine-based curing accelerators, metal-based curing accelerators, and peroxide-based curing accelerators. The curing accelerators may be used alone or in combination of two or more.

[0140] When the resin composition of the present invention contains component (H), the content of component (H) in the resin composition is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and further preferably 1% by mass or more, when the resin component in the resin composition is set to 100% by mass, and the upper limit is preferably 5% by mass or less, more preferably 4% by mass or less, 3% by mass or less, or 2.5% by mass or less.

[0141] <Optional Additives> The resin composition of the present invention may further contain any additives. Examples of such additives include free radical polymerization initiators such as peroxide-based free radical polymerization initiators and azo-based free radical polymerization initiators; thermoplastic resins such as phenoxy resins, polyvinyl acetal resins, polysulfone resins, polyethersulfone resins, polyetheretherketone resins, and polyester resins; organometallic compounds such as organic copper compounds, organic zinc compounds, and organic cobalt compounds; colorants such as phthalocyanine blue, phthalocyanine green, iodine green, diazo yellow, crystal violet, titanium oxide, and carbon black; polymerization inhibitors such as hydroquinone, catechol, pyrogallol, and phenothiazine; leveling agents such as silicone-based leveling agents and acrylic polymer-based leveling agents; thickeners such as Benton (bentonite) and montmorillonite; defoamers such as silicone-based defoamers, acrylic defoamers, fluorine-based defoamers, and vinyl resin-based defoamers; ultraviolet absorbers such as benzotriazole-based ultraviolet absorbers; and adhesives such as urea silane. Improver; adhesion imparting agents such as triazole-based adhesion imparting agents, tetrazole-based adhesion imparting agents, and triazine-based adhesion imparting agents; antioxidants such as hindered phenol-based antioxidants; fluorescent whitening agents such as stilbene derivatives; surfactants such as fluorine-based surfactants and silicone-based surfactants; flame retardants such as phosphorus-based flame retardants (such as phosphate compounds, phosphazene compounds, phosphinic acid compounds, and red phosphorus), nitrogen-based flame retardants (such as melamine sulfate), halogen-based flame retardants, and inorganic flame retardants (such as antimony trioxide); dispersants such as phosphate-based dispersants, polyoxyalkylene-based dispersants, acetylene-based dispersants, silicone-based dispersants, anionic dispersants, and cationic dispersants; stabilizers such as borate-based stabilizers, titanate-based stabilizers, aluminate-based stabilizers, zirconate-based stabilizers, isocyanate-based stabilizers, carboxylic acid-based stabilizers, and carboxylic anhydride-based stabilizers, etc. The content of the additives can be determined according to the characteristics required by the resin composition.

[0142] <Organic Solvents> The resin composition of the present invention may further contain an organic solvent as a volatile component. Examples of the organic solvent include ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ester solvents such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, isoamyl acetate, methyl propionate, ethyl propionate, and γ-butyrolactone; ether solvents such as tetrahydropyran, tetrahydrofuran, 1,4-dioxane, diethyl ether, diisopropyl ether, dibutyl ether, and diphenyl ether; alcohol solvents such as methanol, ethanol, propanol, butanol, and ethylene glycol; 2-ethoxyethyl acetate, propylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, and diethylene glycol ethyl ether acetate. Ether ester solvents such as acetate, γ-butyrolactone, and methyl methoxypropionate; ester alcohol solvents such as methyl lactate, ethyl lactate, and methyl 2-hydroxyisobutyrate; ether alcohol solvents such as 2-methoxypropanol, 2-methoxyethanol, 2-ethoxyethanol, propylene glycol monomethyl ether, and diethylene glycol monobutyl ether (butyl carbitol); amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone; sulfoxide solvents such as dimethyl sulfoxide; nitrile solvents such as acetonitrile and propionitrile; aliphatic hydrocarbon solvents such as hexane, cyclopentane, cyclohexane, and methylcyclohexane; aromatic hydrocarbon solvents such as benzene, toluene, xylene, ethylbenzene, and trimethylbenzene. The organic solvent may be used alone or in combination of two or more.

[0143] Resin combination of the present invention can be, for example, by (A) component, (B) component, (C) component, in addition as required (D) component, (E) component, (F) component, (G) component, (H) component, other additives or organic solvents are added to any preparation container in any order and / or part or all at the same time to mix and manufacture. In addition, in the process of adding each component to mix, the temperature can be appropriately set, and it is also possible to temporarily or always heat and / or cool. In addition, it is also possible to add and mix in the process or afterwards, resin combination, for example, using stirring devices such as stirrers or oscillating devices to stir or vibrate, so that it is evenly dispersed. In addition, it is possible to deaerate under low pressure conditions such as vacuum while stirring or vibrating.

[0144] As described above, the resin composition of the present invention containing the component (C) in combination with the components (A) and (B) can provide a cured product exhibiting good dielectric properties as well as good stain removability and crack resistance.

[0145] In one embodiment, the cured product of the resin composition of the present invention exhibits a low dielectric loss tangent (Df). For example, as described in the <Determination of dielectric loss tangent> column described later, when measured at 5.8 GHz and 23° C., the dielectric loss tangent (Df) of the cured product of the resin composition of the present invention may be preferably 0.0035 or less, 0.0034 or less, 0.0032 or less, 0.003 or less, 0.0028 or less, or 0.0026 or less.

[0146] As described above, the resin composition of the present invention can bring a cured product that exhibits good dielectric properties and good stain removal and crack resistance. Therefore, the resin composition of the present invention can be suitable for use as a resin composition for forming an insulating layer of a printed wiring board (resin composition for insulating layer of a printed wiring board), and is more suitable for use as a resin composition for forming an interlayer insulating layer of a printed wiring board (resin composition for interlayer insulating layer of a printed wiring board). The resin composition of the present invention can also be suitable for use in the case where the printed wiring board is a component built-in wiring board. The resin composition of the present invention can also be suitable for use as a resin composition for forming an insulating layer of a rewiring substrate for semiconductor packaging (resin composition for insulating layer of a rewiring substrate). It should be noted that in the present invention, a printed wiring board or a rewiring substrate is also collectively referred to as a "circuit substrate", and therefore, the resin composition of the present invention can be suitable for use as an insulating layer of a circuit substrate.

[0147] The resin composition of the present invention can also be widely used in applications requiring a resin composition, such as resin sheets, sheet-like laminated materials such as prepregs, solder resists, underfill materials, die bonding materials, hole filling resins, sealing resins, and component embedding resins.

[0148] [Sheet-like laminated materials (resin sheets, prepregs)] The resin composition of the present invention may be used as it is, or may be used in the form of a sheet-like laminated material containing the resin composition.

[0149] As the sheet-like laminated material, the following resin sheets and prepregs are preferred.

[0150] In one embodiment, the resin sheet includes a support and a layer of a resin composition provided on the support (hereinafter simply referred to as a "resin composition layer"), wherein the resin composition layer is formed of the resin composition of the present invention.

[0151] The thickness of the resin composition layer is different according to the different preferred values ​​of the use, and can be appropriately determined according to the use. For example, from the viewpoint of the thinning of a printed wiring board or a semiconductor package, the thickness of the resin composition layer is preferably less than 100 μm, less than 80 μm, less than 60 μm, less than 50 μm, less than 40 μm or less than 30 μm. The lower limit of the thickness of the resin composition layer is not particularly limited, and is usually more than 1 μm, more than 5 μm, etc.

[0152] Examples of the support include thermoplastic resin films, metal foils, and release papers, and thermoplastic resin films and metal foils are preferred. Therefore, in a preferred embodiment, the support is a thermoplastic resin film or a metal foil.

[0153] When a thermoplastic resin film is used as a support, examples of the thermoplastic resin include polyesters such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN), acrylic polymers such as polycarbonate (PC) and polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among them, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.

[0154] When a metal foil is used as a support, examples of the metal foil include copper foil and aluminum foil, preferably copper foil. The copper foil may be a foil made of a single metal such as copper or an alloy of copper and other metals (such as tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.).

[0155] For the support, the surface bonded to the resin composition layer may also be subjected to matte treatment, corona treatment, and antistatic treatment. In addition, as the support, a support with a release layer having a release layer on the surface bonded to the resin composition layer may also be used. As a release agent used in the release layer of the support with a release layer, for example, one or more release agents selected from alkyd resins, polyolefin resins, polyurethane resins, and silicone resins may be cited. The support with a release layer may also use commercial products, for example, "SK-1", "AL-5", "AL-7" made by Lindec Corporation of a PET film having a release layer with an alkyd resin-based release agent as the main component, "Lumirror T60" made by Toray Industries, "Purex" made by Teijin, "Unipeel" made by Unitika, etc.

[0156] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, more preferably in the range of 10 μm to 60 μm. When a support with a release layer is used, the thickness of the entire support with a release layer is preferably in the above range.

[0157] When a metal foil is used as a support, a metal foil with a supporting substrate in which a peelable supporting substrate is bonded to a thin metal foil can be used. In one embodiment, the metal foil with a supporting substrate includes a supporting substrate, a peeling layer provided on the supporting substrate, and a metal foil provided on the peeling layer. When a metal foil with a supporting substrate is used as a support, the resin composition layer is provided on the metal foil.

[0158] In the metal foil with a supporting substrate, the material of the supporting substrate is not particularly limited, and examples thereof include copper foil, aluminum foil, stainless steel foil, titanium foil, copper alloy foil, etc. When copper foil is used as the supporting substrate, it may be electrolytic copper foil or rolled copper foil. In addition, the peeling layer is not particularly limited as long as the metal foil can be peeled off from the supporting substrate, and examples thereof include alloy layers of elements selected from Cr, Ni, Co, Fe, Mo, Ti, W, and P; organic films, etc.

[0159] In the metal foil with a supporting substrate, the material of the metal foil is preferably, for example, copper foil or copper alloy foil.

[0160] In the metal foil with a supporting substrate, the thickness of the supporting substrate is not particularly limited, but is preferably in the range of 10 μm to 150 μm, more preferably in the range of 10 μm to 100 μm. The thickness of the metal foil may be, for example, in the range of 0.1 μm to 10 μm.

[0161] In one embodiment, the resin sheet may further include an arbitrary layer as required. As the arbitrary layer, for example, a protective film disposed on the surface of the resin composition layer that is not bonded to the support (i.e., the surface on the opposite side of the support) may be cited. The thickness of the protective film is not particularly limited, for example, it may be 1 μm to 40 μm. By laminating the protective film, it is possible to suppress the attachment of garbage or the like on the surface of the resin composition layer or the generation of damage.

[0162] The resin sheet can be produced, for example, by directly coating a liquid resin composition on a support using a die coater or the like, or by preparing a resin varnish prepared by dissolving the resin composition in an organic solvent and coating the varnish on a support, followed by drying to form a resin composition layer.

[0163] Examples of the organic solvent include the same organic solvents as those described as components of the resin composition. The organic solvent may be used alone or in combination of two or more.

[0164] Drying can be carried out by known methods such as heating and hot air blowing. The drying conditions are not particularly limited, and the drying is carried out in a manner such that the content of the organic solvent in the resin composition layer is 10% by mass or less, preferably 5% by mass or less. The drying conditions also vary depending on the boiling point of the organic solvent in the resin composition or resin varnish. For example, when using a resin composition or resin varnish containing 30% to 60% by mass of an organic solvent, the resin composition layer can be formed by drying at 50° C. to 150° C. for 3 minutes to 10 minutes.

[0165] The resin sheet can be stored by being wound into a roll. When the resin sheet has a protective film, it can be used by peeling off the protective film.

[0166] In one embodiment, the prepreg is formed by impregnating the resin composition of the present invention into a sheet-like fiber base material.

[0167] The sheet-like fiber substrate used for the prepreg is not particularly limited, and materials commonly used as prepreg substrates such as glass cloth, aramid nonwoven fabric, and liquid crystal polymer nonwoven fabric can be used. From the perspective of thinning of printed wiring boards or semiconductor chip packages, the thickness of the sheet-like fiber substrate is preferably 50 μm or less, more preferably 40 μm or less, more preferably 30 μm or less, and particularly preferably 20 μm or less. The lower limit of the thickness of the sheet-like fiber substrate is not particularly limited. It is usually 10 μm or more.

[0168] The prepreg can be produced by a known method such as a hot melt method or a solvent method.

[0169] The thickness of the prepreg may be in the same range as that of the resin composition layer in the above-mentioned resin sheet.

[0170] The sheet-like laminated material of the present invention can be suitable for forming an insulating layer of a printed wiring board (for an insulating layer of a printed wiring board), and can be more suitable for forming an interlayer insulating layer of a printed wiring board (for an interlayer insulating layer of a printed wiring board). The sheet-like laminated material of the present invention can also be suitable for forming an insulating layer of a rewiring substrate of a semiconductor package (for an insulating layer of a rewiring substrate). That is, the sheet-like laminated material of the present invention can be suitable for use as an insulating layer of a circuit substrate.

[0171] [Circuit board] The resin composition of the present invention can be used to form an insulating layer of a circuit board. The present invention also provides the circuit board, that is, a circuit board including an insulating layer formed of a cured product of the resin composition of the present invention.

[0172] <Printed wiring board> In one embodiment, the circuit substrate of the present invention is a printed wiring board.

[0173] The printed wiring board can be produced, for example, by using the above-mentioned resin sheet and by a method comprising the following steps (I) and (II). (I) a step of laminating a resin sheet on the inner layer substrate so that the resin composition layer of the resin sheet is bonded to the inner layer substrate; and (II) a step of curing (for example, thermally curing) the resin composition layer to form an insulating layer.

[0174] The "inner substrate" used in step (I) is a member of the substrate that forms the printed wiring board, and examples thereof include: glass epoxy substrate, metal substrate, polyester substrate, polyimide substrate, BT resin substrate, thermosetting polyphenylene ether substrate, etc. In addition, the substrate may have a conductor layer on one or both sides thereof, and the conductor layer may also be patterned. An inner substrate having a conductor layer (circuit) formed on one or both sides of the substrate is sometimes referred to as an "inner circuit substrate". In addition, when manufacturing a printed wiring board, an intermediate product to be further formed with an insulating layer and / or a conductor layer is also included in the "inner substrate" described in the present invention. In the case where the printed wiring board is a circuit board with built-in components, an inner substrate with built-in components may also be used.

[0175] The lamination of the inner substrate and the resin sheet can be performed, for example, by heat-pressing the resin sheet onto the inner substrate from the support body side. As a member for heat-pressing the resin sheet onto the inner substrate (hereinafter also referred to as a "heat-pressing member"), for example, a heated metal plate (SUS end plate, etc.) or a metal roller (SUS roller) can be cited. It should be noted that the heat-pressing member can be directly pressed onto the resin sheet, or it can be pressed via an elastic material such as heat-resistant rubber so that the resin sheet fully follows the surface unevenness of the inner substrate.

[0176] The lamination of the inner substrate and the resin sheet can be implemented by vacuum lamination. In the vacuum lamination, the heating and pressing temperature is preferably 60°C to 160°C, more preferably in the range of 80°C to 140°C, the heating and pressing pressure is preferably 0.098MPa to 1.77MPa, more preferably in the range of 0.29MPa to 1.47MPa, and the heating and pressing time is preferably 20 seconds to 400 seconds, more preferably in the range of 30 seconds to 300 seconds. Lamination can be preferably implemented under reduced pressure conditions of 26.7hPa or less.

[0177] Lamination can be performed by a commercially available vacuum laminator. Examples of the commercially available vacuum laminator include a vacuum pressure laminator manufactured by Meiki Seisakusho Co., Ltd., a vacuum laminator manufactured by Nikko-Materials Co., Ltd., and a batch vacuum pressure laminator.

[0178] After lamination, the laminated resin sheet can be smoothed under normal pressure (atmospheric pressure), for example, by pressing the heating and pressing member from the support body side. The pressing conditions for the smoothing treatment can be the same as the heating and pressing conditions for the above-mentioned lamination. The smoothing treatment can be performed using a commercially available laminator. It should be noted that the lamination and smoothing treatment can also be performed continuously using the above-mentioned commercially available vacuum laminator.

[0179] The support may be removed between step (I) and step (II), or after step (II). It should be noted that when a metal foil is used as the support, the metal foil may be used to form the conductor layer without peeling off the support. In addition, when a metal foil with a supporting substrate is used as the support, the supporting substrate (and the peeling layer) may be peeled off. Furthermore, the conductor layer may be formed using the metal foil.

[0180] In step (II), the resin composition layer is cured (eg, thermally cured) to form an insulating layer formed of a cured product of the resin composition. The curing conditions of the resin composition layer are not particularly limited, and conditions generally used when forming an insulating layer of a printed wiring board can be used.

[0181] For example, the heat curing conditions of the resin composition layer vary depending on the type of the resin composition, but in one embodiment, the curing temperature is preferably 140° C. to 250° C., more preferably 150° C. to 240° C., and further preferably 160° C. to 230° C. The curing time is preferably 5 minutes to 240 minutes, more preferably 10 minutes to 150 minutes, and further preferably 15 minutes to 120 minutes.

[0182] Before the resin composition layer is thermally cured, the resin composition layer may be preheated at a temperature lower than the curing temperature. For example, before the resin composition layer is thermally cured, the resin composition layer may be preheated at a temperature of 50°C to 140°C, preferably 60°C to 135°C, more preferably 70°C to 130°C, for 5 minutes or more, preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and even more preferably 15 minutes to 100 minutes.

[0183] When manufacturing a printed wiring board, it is also possible to further implement the process of (III) opening a hole in the insulating layer, the process of (IV) roughening the insulating layer, and the process of (V) forming a conductor layer. These processes (III) to (V) can be implemented according to various methods known to those skilled in the art used in the manufacture of printed wiring boards. It should be noted that when the support is removed after process (II), the removal of the support can be implemented between process (II) and process (III), between process (III) and process (IV), or between process (IV) and process (V). In addition, as needed, the formation of the insulating layer and the conductor layer of processes (I) to (V) can also be repeatedly implemented to form a multilayer wiring board.

[0184] In other embodiments, the printed wiring board of the present invention can be produced using the above-mentioned prepreg. The production method is basically the same as that in the case of using a resin sheet.

[0185] Step (III) is a step of opening a hole in the insulating layer, thereby forming a hole such as a viahole or a through hole in the insulating layer. Step (III) can be implemented, for example, using a drill, a laser, a plasma, etc., depending on the composition of the resin composition used in the formation of the insulating layer. The size and shape of the hole can be appropriately determined according to the design of the printed wiring board.

[0186] Step (IV) is a step of roughening the insulating layer. Usually, in step (IV), contamination removal (decontamination) is also performed. The order and conditions of the roughening treatment are not particularly limited, and the known order and conditions commonly used when forming the insulating layer of the printed wiring board can be adopted. For example, the insulating layer can be roughened by swelling treatment using a swelling solution, roughening treatment using an oxidant, and neutralization treatment using a neutralizing solution.

[0187] The swelling liquid used in the roughening treatment is not particularly limited, and examples thereof include alkaline solutions, surfactant solutions, etc., preferably alkaline solutions, and more preferably sodium hydroxide solutions and potassium hydroxide solutions. Commercially available swelling liquids include, for example, "Swelling Dip Securiganth P" and "Swelling Dip Securiganth SBU" manufactured by Atotech Japan Co., Ltd. The swelling treatment using the swelling liquid is not particularly limited, and for example, it can be performed by immersing the insulating layer in a swelling liquid at 30°C to 90°C for 1 minute to 20 minutes. From the viewpoint of controlling the swelling of the resin of the insulating layer to an appropriate level, it is preferred that the insulating layer be immersed in a swelling liquid at 40°C to 80°C for 5 minutes to 15 minutes.

[0188] As the oxidant used in the roughening treatment, there is no particular limitation, and an alkaline permanganate solution formed by dissolving potassium permanganate or sodium permanganate in an aqueous solution of sodium hydroxide can be cited. The roughening treatment using an oxidant such as an alkaline permanganate solution is preferably carried out by immersing the insulating layer in an oxidant solution heated to 60°C to 100°C for 10 minutes to 30 minutes. In addition, the concentration of permanganate in the alkaline permanganate solution is preferably 5% by mass to 10% by mass. As commercially available oxidants, alkaline permanganate solutions such as "Concentrate Compact CP", "Concentrate Compact P", and "Dosing Solution Securiganth P" manufactured by Atotech Japan Co., Ltd. can be cited.

[0189] The neutralizing solution used in the roughening treatment is preferably an acidic aqueous solution, and examples of commercially available products include "Reduction Solution Securiganth P" manufactured by Atotech Japan Co., Ltd.

[0190] The treatment with the neutralizing solution can be performed by immersing the surface roughened with the oxidizing agent in the neutralizing solution at 30° C. to 80° C. for 5 to 30 minutes. In view of operability, it is preferred to immerse the object roughened with the oxidizing agent in the neutralizing solution at 40° C. to 70° C. for 5 to 20 minutes.

[0191] Step (V) is a step of forming a conductor layer, and a conductor layer is formed on the insulating layer. The conductor material used for the conductor layer is not particularly limited. In a preferred embodiment, the conductor layer comprises one or more metals selected from gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin and indium. The conductor layer can be a single metal layer or an alloy layer. As the alloy layer, for example, a layer formed by an alloy of two or more metals selected from the above metals (for example, a nickel-chromium alloy, a copper-nickel alloy and a copper-titanium alloy) can be cited. Among them, from the viewpoints of versatility, cost, ease of pattern formation, etc. of the formation of the conductor layer, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver or copper, or an alloy layer of nickel-chromium alloy, copper-nickel alloy, or copper-titanium alloy is preferred, and a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver or copper, or an alloy layer of nickel-chromium alloy is more preferred, and a single metal layer of copper is more preferred.

[0192] The conductor layer may be a single-layer structure or a multi-layer structure in which two or more single metal layers or alloy layers formed of different types of metals or alloys are stacked. In the case where the conductor layer is a multi-layer structure, the layer in contact with the insulating layer is preferably a single metal layer of chromium, zinc or titanium or an alloy layer of a nickel-chromium alloy.

[0193] The thickness of the conductor layer varies depending on the desired design of the printed wiring board, but is generally 3 μm to 35 μm, preferably 5 μm to 30 μm.

[0194] In one embodiment, the conductor layer can be formed by plating. From the viewpoint of facilitating the formation of fine wiring, it is preferably formed by a semi-additive method. An example of forming a conductor layer by a semi-additive method is shown below.

[0195] First, a plating seed layer is formed on the surface of the insulating layer by electroless plating. Next, a mask pattern is formed on the formed plating seed layer to expose a portion of the plating seed layer corresponding to the desired wiring pattern. After a metal layer is formed on the exposed plating seed layer by electrolytic plating, the mask pattern is removed. Then, the unnecessary plating seed layer is removed by etching or the like, thereby forming a conductor layer having a desired wiring pattern.

[0196] In other embodiments, the conductor layer can be formed using a metal foil. When a metal foil is used to form a conductor layer, it is preferred to implement step (V) between step (I) and step (II). For example, after step (I), the support is removed and a metal foil is laminated on the surface of the exposed resin composition layer. The lamination of the resin composition layer and the metal foil can be implemented by a vacuum lamination method. The lamination conditions can be the same as those described for step (I). Next, step (II) is implemented to form an insulating layer. Then, using the metal foil on the insulating layer, a conductor layer with a desired wiring pattern can be formed by a conventionally known technique such as a modified semi-additive method.

[0197] The metal foil can be produced by a known method such as electrolysis or rolling. Commercially available metal foils include HLP foil and JXUT-III foil manufactured by JX Metals, and 3EC-III foil and TP-III foil manufactured by Mitsui Mining & Smelting Co., Ltd.

[0198] Alternatively, as described above, when a metal foil or a metal foil with a supporting substrate is used as the support of the resin sheet, the conductor layer can be formed using the metal foil.

[0199] <Rewiring substrate for semiconductor package> In one embodiment, the circuit substrate of the present invention is a rewiring substrate (rewiring layer) of a semiconductor package. Hereinafter, the circuit substrate will be described in conjunction with a method for manufacturing a semiconductor package.

[0200] The semiconductor package includes an insulating layer formed of a cured product of the resin composition of the present invention as an insulating layer of a rewiring board. In addition, the semiconductor package may include a sealing layer formed of a cured product of the resin composition of the present invention.

[0201] A semiconductor package can be manufactured, for example, using the resin composition and resin sheet of the present invention by a method comprising the following steps (1) to (6). The resin composition and resin sheet of the present invention can be used to form a rewiring forming layer (an insulating layer for forming a rewiring substrate) in step (5) or a sealing layer in step (3). An example of forming a rewiring forming layer or a sealing layer using a resin composition or a resin sheet is shown below, but the technology for forming a rewiring forming layer or a sealing layer of a semiconductor package is well known, and a person skilled in the art can use the resin composition or resin sheet of the present invention to manufacture a semiconductor package according to well-known techniques; (1) a step of laminating a temporary fixing film on a substrate, (2) a step of temporarily fixing the semiconductor chip on a temporary fixing film, (3) a step of forming a sealing layer on a semiconductor chip, (4) a step of peeling the substrate and the temporary fixing film from the semiconductor chip, (5) forming a rewiring forming layer as an insulating layer on the surface of the semiconductor chip from which the substrate and the temporary fixing film have been peeled off, and (6) A step of forming a rewiring layer as a conductor layer on the rewiring formation layer.

[0202] -Process (1)- The material used in the substrate is not particularly limited. Examples of the substrate include semiconductor wafers such as silicon wafers; glass wafers; glass substrates; metal substrates such as copper, titanium, stainless steel, and cold-rolled steel sheets (SPCC); substrates in which epoxy resins or the like are impregnated into glass fibers and heat-cured (e.g., FR-4 substrates); substrates formed from bismaleimide triazine resins (BT resins), and the like.

[0203] The temporary fixing film may be made of any material as long as it can be peeled off from the semiconductor chip in step (4) and can temporarily fix the semiconductor chip. A commercially available product may be used as the temporary fixing film. Examples of commercially available products include REVALPHA manufactured by Nitto Denko Corporation.

[0204] -Process (2)- The temporary fixation of the semiconductor chip can be performed using a known device such as a flip chip bonder or a die bonder. The layout and number of semiconductor chips can be appropriately set according to the shape and size of the temporary fixation film, the number of semiconductor packages to be produced, etc. For example, the semiconductor chips can be arranged in a matrix of multiple rows and columns for temporary fixation.

[0205] -Process (3)- The resin composition layer of the resin sheet of the present invention is laminated on a semiconductor chip, or the resin composition of the present invention is applied on a semiconductor chip and cured (for example, thermally cured) to form a sealing layer.

[0206] For example, the stacking of semiconductor chips and resin sheets can be performed by heating and pressing the resin sheets on the semiconductor chips from the support side after removing the protective film of the resin sheets. As a component for heating and pressing the resin sheets on the semiconductor chips (hereinafter also referred to as "heating and pressing components"), for example, heated metal plates (SUS end plates, etc.) or metal rollers (SUS rollers) can be cited. It should be noted that it is preferred that the heating and pressing components are not directly pressed on the resin sheets, but are pressed via elastic materials such as heat-resistant rubber so that the resin sheets fully follow the surface unevenness of the semiconductor chips. The stacking of semiconductor chips and resin sheets can also be implemented by vacuum lamination, and the stacking conditions are the same as the stacking conditions described for the method for manufacturing printed wiring boards, and the preferred range is also the same.

[0207] After lamination, the resin composition is thermally cured to form a sealing layer. The thermal curing conditions are the same as those described in the method for producing a printed wiring board.

[0208] The support of the resin sheet may be peeled off after laminating the resin sheet on the semiconductor chip and thermally curing it, or the support may be peeled off before laminating the resin sheet on the semiconductor chip.

[0209] When the resin composition of the present invention is applied to form a sealant layer, the application conditions are the same as those for forming the resin composition layer described in relation to the resin sheet of the present invention, and the preferred ranges are also the same.

[0210] -Process (4)- The method of peeling off the substrate and the temporary fixing film can be appropriately changed according to the material of the temporary fixing film, and examples thereof include a method of peeling off the temporary fixing film by heating and foaming (or expanding) the temporary fixing film, and a method of peeling off the temporary fixing film by irradiating ultraviolet rays from the substrate side to reduce the adhesion of the temporary fixing film.

[0211] In the method of peeling off by heating the temporary fixing film to foam (or expand), the heating conditions are usually 100 to 250°C for 1 to 90 seconds or 5 to 15 minutes. In the method of peeling off by irradiating ultraviolet rays from the substrate side to reduce the adhesive force of the temporary fixing film, the irradiation amount of ultraviolet rays is usually 10 mJ / cm 2 ~1000mJ / cm 2 .

[0212] -Process (5)- The resin composition and the resin sheet of the present invention are used to form a rewiring forming layer (insulating layer of a rewiring board).

[0213] After the rewiring formation layer is formed, a through hole may be formed in the rewiring formation layer in order to connect the semiconductor chip to the conductor layer described later. The through hole can be formed by a known method depending on the material of the rewiring formation layer.

[0214] -Process (6)- The formation of the conductor layer on the rewiring forming layer can be carried out in the same manner as step (V) described in the method for manufacturing a printed wiring board. It should be noted that steps (5) and (6) may be repeated to alternately overlap (stack) the conductor layer (rewiring layer) and the rewiring forming layer (insulating layer).

[0215] When manufacturing a semiconductor package, further steps may be performed such as (7) forming a solder resist layer on a conductor layer (rewiring layer), (8) forming bumps, and (9) cutting a plurality of semiconductor packages into individual semiconductor packages for singulation. These steps may be performed according to various methods known to those skilled in the art used in the manufacture of semiconductor packages.

[0216] By using the resin composition and resin sheet of the present invention that can bring a cured product that presents good dielectric properties and good contamination removal and crack resistance at the same time, a rewiring formation layer (insulating layer) is formed, so that the semiconductor package, whether it is a fan-in (Fan-In) type package or a fan-out (Fan-Out) type package, can achieve a semiconductor package with very little transmission loss without worrying about cracks. In one embodiment, the semiconductor package of the present invention is a fan-out (Fan-Out) type package. For the resin composition and resin sheet of the present invention, whether it is a fan-out panel level package (FOPLP) or a fan-out wafer level package (FOWLP), it can be applied. In one embodiment, the semiconductor package of the present invention is a fan-out panel level package (FOPLP) or a fan-out wafer level package (FOWLP).

[0217] [Semiconductor devices] The semiconductor device of the present invention includes a layer formed of a cured product of the resin composition layer of the present invention. The semiconductor device of the present invention can be produced using the circuit board of the present invention.

[0218] Examples of the semiconductor device include various semiconductor devices used in electrical products (eg, computers, mobile phones, digital cameras, and televisions) and vehicles (eg, motorcycles, cars, trains, ships, and airplanes). Example

[0219] The present invention will be specifically described below by way of examples. The present invention is not limited to these examples. It should be noted that, below, "parts" and "%" indicating amounts refer to "parts by mass" and "% by mass" respectively, unless otherwise indicated.

[0220] <Synthesis Example 1: Synthesis of Active Ester Resin A> In a flask equipped with a thermometer, a dropping funnel, a condenser, a fractionating tube, and a stirrer, 203.0 g of isophthaloyl chloride (the number of moles of acyl chloride groups: 2.0 moles) and 1400 g of toluene are added, and the system is replaced with nitrogen under reduced pressure and dissolved. Next, 113.9 g (0.67 moles) of o-phenylphenol and 240 g (the number of moles of phenolic hydroxyl groups: 1.33 moles) of dihydroxynaphthalene with a benzyl group are added, and the system is replaced with nitrogen under reduced pressure and dissolved. Then, 0.70 g of tetrabutylammonium bromide is dissolved, and while nitrogen is purged, the system is controlled at below 60°C, and 400 g of a 20% aqueous sodium hydroxide solution is added dropwise over 3 hours. Then, stirring is continued for 1.0 hour under this condition. After the reaction is completed, the liquid is allowed to stand and the water layer is removed. Water is then added to the toluene layer in which the reactants are dissolved, and the mixture is stirred and mixed for 15 minutes, and the liquid is allowed to stand and the water layer is removed. This operation is repeated until the pH value of the water layer reaches 7. Then, water was removed by decanting to obtain an active ester resin A (active ester resin containing a naphthalene structure) in a toluene solution state with a nonvolatile content of 65% by mass. The active ester group equivalent of the obtained active ester resin A was 238 g / eq.

[0221] <Synthesis Example 2: Synthesis of Maleimide Compound A> According to the synthesis example 1 of the Japanese Invention Association's Public Technical Bulletin No. 2020-500211, a MEK solution of a maleimide compound A represented by the following formula (M) (non-volatile component 62% by mass) was prepared. The Mw / Mn of the maleimide compound A is 1.81, and t" in the formula (M) is 1.47 (mainly 1, 2 or 3).

[0222] [Chemical formula 9]

[0223] <Synthesis Example 3: Synthesis of Vinyl Compound A> According to Example 1 of International Publication No. 2017 / 115813, 3.0 mol (390.6 g) of divinylbenzene, 1.8 mol (229.4 g) of ethylvinylbenzene, 10.2 mol (1066.3 g) of styrene, and 15.0 mol (1532.0 g) of n-propyl acetate were put into a 5.0 L reactor, and 600 mmol of diethyl ether complex of boron trifluoride was added at 70 ° C, and the reaction was carried out for 4 hours. After the polymerization solution was stopped with an aqueous sodium bicarbonate solution, the oil layer was washed 3 times with pure water, and the polymer was recovered by decompression and devolatilization at 60 ° C. The obtained substance was weighed, and 896.7 g of vinyl compound A was confirmed. The Mw of vinyl compound A is 41300.

[0224] [Examples 1 to 9, Comparative Examples 1 to 3] (1) Preparation of resin composition Each component was weighed according to the blending composition described in Table 1, and 10 parts of MEK and 10 parts of cyclohexanone were further mixed and uniformly dispersed using a high-speed rotary mixer to obtain a resin composition (resin varnish).

[0225] (2) Manufacture of resin sheets As a support, a polyethylene terephthalate film ("AL5" manufactured by Lintec Corporation, thickness 38 μm) having a release layer was prepared. The obtained resin varnish was evenly coated on the release layer of the support so that the thickness of the resin composition layer after drying was 40 μm. Then, the resin composition was dried at 80°C to 100°C (average 90°C) for 4 minutes to obtain a resin sheet A having a layer structure of resin composition layer / support. Moreover, the resin sheet B was obtained similarly to the above except having applied the resin varnish uniformly so that the thickness of the resin composition layer after drying might be 25 micrometers.

[0226] <Measurement of dielectric loss tangent> The resin sheet A obtained in the examples and comparative examples was heated in an oven at 190°C for 90 minutes to cure the resin composition layer. Then, the support was peeled off to obtain a cured product of the resin composition layer. The cured product was cut into pieces of 80 mm in length and 2 mm in width to prepare a cured product for evaluation.

[0227] For each evaluation cured product, the dielectric loss tangent value (Df value) was measured by a cavity perturbation method using "HP8362B" manufactured by Agilent Technologies at a measurement frequency of 5.8 GHz and a measurement temperature of 23° C. The measurement was performed on two test pieces, and the average value was calculated.

[0228] <Evaluation of stain removability> (1) Preparation of inner substrate Both sides of a glass cloth-based epoxy resin double-sided copper-clad laminate (copper foil thickness 18 μm, substrate thickness 0.4 mm, "R1515A" manufactured by Panasonic) with an inner layer circuit formed thereon were etched 1 μm with a microetchant ("CZ8101" manufactured by MEC) to roughen the copper surface.

[0229] (2) Lamination of resin sheets A The resin sheet A obtained in the examples and comparative examples was laminated on both sides of the inner substrate in such a way that the resin composition layer was in contact with the inner substrate using a batch vacuum press laminator (Nikko-Materials, 2-stage stack laminator "CVP700"). Lamination was performed by reducing the pressure for 30 seconds to adjust the air pressure to 13 hPa or less, and then pressing at 120°C and a pressure of 0.74 MPa for 30 seconds. Then, hot pressing was performed at 100°C and a pressure of 0.5 MPa for 60 seconds for smoothing.

[0230] (3) Thermal curing of resin composition layer Then, the inner substrate laminated with the resin sheet A was placed in an oven at 130°C and heated for 30 minutes, and then transferred to an oven at 170°C and heated for 30 minutes to thermally cure the resin composition layer to form an insulating layer. Then, the support was peeled off to obtain a cured substrate having a structure of insulating layer / inner substrate / insulating layer.

[0231] (4) Formation of through holes For the obtained cured substrate, use CO 2 The insulating layer was subjected to hole drilling by a laser processing machine (LK-2K212 / 2C manufactured by Via Machine Co., Ltd.) under the conditions of a frequency of 2000 Hz, a pulse width of 3 microseconds, an output power of 0.95 W, and an irradiation (shot) number of 3. Thus, through holes having a top diameter (diameter) of 50 μm on the surface of the insulating layer and a diameter of 50 μm on the bottom surface of the insulating layer were formed, and substrate A was obtained.

[0232] (5) Roughening treatment A desmear treatment as a roughening treatment was performed on the substrate A. As the desmear treatment, the following wet desmear treatment was performed. (Wet decontamination treatment) The cured substrate was immersed in a swelling solution ("Swelling Dip Securiganth P" manufactured by Atotech Japan, an aqueous solution of diethylene glycol monobutyl ether and sodium hydroxide) at 60°C for 10 minutes, then immersed in an oxidant solution ("Concentrate Compact P" manufactured by Atotech Japan, an aqueous solution of about 6% potassium permanganate and about 4% sodium hydroxide) at 80°C for 25 minutes, and finally immersed in a neutralizing solution ("Reduction Solution Securiganth P" manufactured by Atotech Japan, an aqueous solution of sulfuric acid) at 40°C for 5 minutes. Then, it was dried at 80°C for 15 minutes. The resulting substrate was called evaluation substrate A.

[0233] (6) Evaluation of stain removal properties The evaluation substrate A was observed around the bottom of the through hole using a scanning electron microscope (SEM), and the maximum contamination length from the wall surface of the through hole bottom was measured from the obtained image, and evaluated based on the following criteria. ○: Maximum contamination length is less than 5μm ×: Maximum contamination length is 5 μm or more

[0234] <Evaluation of Crack Resistance after Decontamination Treatment> (1) Preparation of inner substrate As a core material, a core material ("E705GR" manufactured by Resonac, thickness 400 μm) was prepared in which circular copper pads (copper thickness 35 μm) with a diameter of 350 μm were formed in a lattice at intervals of 400 μm so that the residual copper ratio became 60%.

[0235] (2) Lamination of resin sheets B The resin sheet B obtained in the examples and comparative examples was laminated on both sides of the inner substrate in such a manner that the resin composition layer was in contact with the inner substrate using a batch vacuum press laminator (Nikko-Materials, 2-stage stack laminator "CVP700"). The lamination was performed by reducing the pressure for 30 seconds to adjust the air pressure to 13 hPa or less, and then pressing at 100°C and a pressure of 0.74 MPa for 30 seconds. Then, the sheet was smoothed by hot pressing at 100°C and a pressure of 0.5 MPa for 60 seconds.

[0236] (3) Thermal curing of resin composition layer Then, the inner substrate laminated with the resin sheet B was placed in an oven at 130°C and heated for 30 minutes, and then transferred to an oven at 175°C and heated for 40 minutes to thermally cure the resin composition layer to form an insulating layer. Then, the support was peeled off to obtain a cured substrate having a structure of insulating layer / inner substrate / insulating layer.

[0237] (4) Decontamination treatment The obtained cured substrate was immersed in a swelling solution ("Swelling Dip Securiganth P" manufactured by Atotech Japan, an aqueous solution of diethylene glycol monobutyl ether and sodium hydroxide) at 60°C for 5 minutes, then immersed in an oxidant solution ("Concentrate Compact P" manufactured by Atotech Japan, an aqueous solution of about 6% potassium permanganate and about 4% sodium hydroxide) at 80°C for 30 minutes, and finally immersed in a neutralizing solution ("Reduction Solution Securiganth P" manufactured by Atotech Japan, an aqueous solution of sulfuric acid) at 40°C for 5 minutes. Then, it was dried at 80°C for 15 minutes. The obtained substrate is called evaluation substrate B.

[0238] (5) Evaluation of crack resistance About the evaluation substrate B, 100 copper pads were observed to check the presence or absence of cracks in the insulating layer, and evaluation was performed based on the following criteria. ○: 10 or fewer cracks ×: More than 10 cracks

[0239] Table 1 shows the results of Examples 1 to 9 and Comparative Examples 1 to 3.

[0240] [Table 1]

[0241] In addition, the details of each component described in Table 1 are as follows. (A) Epoxy resin ·ZX1059: Functional group equivalent weight 169 g / eq, manufactured by Nippon Steel Chemicals Co., Ltd., 1:1 mixture of bisphenol A epoxy resin and bisphenol F epoxy resin HP-4032-SS: Functional group equivalent 144 g / eq, manufactured by DIC Corporation, naphthalene-based epoxy resin NC-3000L: Functional group equivalent 269g / eq, manufactured by Nippon Kayaku Co., Ltd., biphenyl type epoxy resin (B) Active ester resin HPC-8150-62T: functional group equivalent 223 g / eq, toluene solution with a nonvolatile content of 61.5% by mass, manufactured by DIC Corporation, an active ester resin having a naphthalene structure HPC-8000L-65MT: functional group equivalent 229 g / eq, toluene / MEK solution with a nonvolatile content of 65% by mass, manufactured by DIC Corporation, active ester resin containing a dicyclopentadiene-type diphenol structure Active ester resin A: the active ester resin synthesized in Synthesis Example 1 -(C) (meth)acrylate compound containing an aliphatic group having 10 or more carbon atoms- PEAM1769: a (meth)acrylate compound having a structure represented by the following formula (C-1) manufactured by Designer Molecules Inc. (wherein R S1 C 8 Alkyl, R S2 C 5 or C 6 Alkyl, n is 1 to 5) [Chemical formula 10] (D) Other curing agents LA-3018-50P: 1-methoxy-2-propanol solution containing 50% by mass of nonvolatile components, manufactured by DIC Corporation (E) Inorganic filling materials SO-C2: Spherical silica surface-treated with an amino-based silane coupling agent ("KBM573" manufactured by Shin-Etsu Chemical Co., Ltd.), average particle size 0.5 μm, specific surface area 5.8 m 2 / g, made by Yaduma (F) Compounds containing a radically polymerizable unsaturated group Maleimide compound A: the maleimide compound synthesized in Synthesis Example 2 MIR-3000-70MT: a toluene / MEK solution containing 70% by mass of nonvolatile matter, manufactured by Nippon Kayaku Co., Ltd., a maleimide compound having a structure represented by the following formula and containing an aromatic ring skeleton directly bonded to the nitrogen atom of the maleimide group (wherein n is 1 to 100): [Chemical formula 11] SLK-6895: Made by Shin-Etsu Chemical Co., Ltd., a maleimide compound containing an aliphatic skeleton SLK-1500: Made by Shin-Etsu Chemical Co., Ltd., a maleimide compound containing an aliphatic skeleton OPE-2St-1200: Toluene solution containing 65% by mass of nonvolatile matter, manufactured by Mitsubishi Gas Chemical Co., Ltd. Vinyl compound A: the vinyl compound synthesized in Synthesis Example 3 NE-V-1100-70T: Toluene solution containing 70% by mass of nonvolatile components, manufactured by DIC Corporation ·A-DOG: Made by Shin-Nakamura Chemical Industry Co., Ltd. -(G) Organic filling materials- EXL-2655: Made by Dow Chemical, an organic filler containing rubber components -(H) Curing accelerator- 1B2PZ: manufactured by Shikoku Chemical Industry Co., Ltd., an imidazole-based curing accelerator.

Claims

1. A resin composition, wherein Include: (A) Epoxy resin, (B) an active ester resin, and (C) A (meth)acrylate compound containing an aliphatic group having 10 or more carbon atoms.

2. The resin composition according to claim 1, wherein The mass ratio of the component (B) to the component (A), that is, the component (B) / component (A) is 0.8 or more.

3. The resin composition according to claim 1, wherein When the resin component in the resin composition is 100 mass %, content of the component (C) is 0.5 mass % or more.

4. The resin composition according to claim 1, wherein The component (C) contains a divalent aliphatic group represented by the following formula (1): In formula (1), A C Each independently represents a single bond or a divalent aliphatic group, Ring Z C represents an aliphatic ring optionally having a substituent, * indicates a bond, 2 A C and Ring Z C The total number of carbon atoms is 10 or more.

5. The resin composition according to claim 1, wherein The component (C) has a structure represented by the following formula (C1), In formula (C1), X each independently represents a (meth)acryloyl group, A 1 Each independently represents a divalent aliphatic group, A 2 each independently represents a divalent aliphatic group having 10 or more carbon atoms, L 1 Each independently represents a divalent linking group, n1 represents a number greater than or equal to 1.

6. The resin composition according to claim 1, wherein The component (C) has a structure represented by the following formula (C1-1), In formula (C1-1), X each independently represents a (meth)acryloyl group, A 11 each independently represents an alkylene group having 1 to 12 carbon atoms, A 21 each independently represents an alkylene group having 1 to 12 carbon atoms or an alkenylene group having 2 to 12 carbon atoms, Ring Z 1 each independently represents a cycloalkane ring having 4 to 14 carbon atoms which may have a substituent, Ring Z 2 each independently represents a cycloalkane ring having 4 to 14 carbon atoms which may have a substituent or a cycloalkene ring having 4 to 14 carbon atoms which may have a substituent, n11 represents a number from 1 to 10.

7. The resin composition according to claim 6, wherein In formula (C1-1), X each independently represents a (meth)acryloyl group, A 11 represents an alkylene group having 1 carbon atom, A 21 represents an alkylene group having 7 carbon atoms, Ring Z 1 represents a tricyclodecane ring, Ring Z 2 represents a cyclohexane ring substituted with two alkyl groups having 5 to 8 carbon atoms, n11 represents a number from 1 to 5.

8. The resin composition according to claim 1, wherein The composition further comprises (E) an inorganic filler.

9. The resin composition according to claim 8, wherein When the nonvolatile matter in the resin composition is 100 mass %, the content of the component (E) is 40 mass % or more.

10. The resin composition according to claim 1, wherein The invention further comprises (F) a compound containing a radically polymerizable unsaturated group, wherein the component (F) is a component other than the component (C). The resin composition according to claim 1 , which is used for an insulating layer of a circuit board.

12. A resin sheet, wherein: A layer comprising a support and the resin composition according to any one of claims 1 to 11 provided on the support.

13. The resin sheet according to claim 12, wherein The support is a thermoplastic resin film or a metal foil.

14. A cured product of the resin composition according to any one of claims 1 to 11.

15. A circuit substrate, wherein: The present invention comprises an insulating layer formed of a cured product of the resin composition according to any one of claims 1 to 11.

16. A semiconductor device, wherein: A circuit substrate comprising the circuit substrate according to claim 15.